Effects of Dietary Eucommia ulmoides Leaf Extract on Growth, Muscle Composition, Hepatopancreas Histology, Immune Responses and Microcystin-LR Resistance of Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Yao-Peng Lu; Pei-Hua Zheng; Jia-Rui Xu; Yan-Lei Cao; Jun-Tao Li; Chen-Guang Hao; Ze-Long Zhang; Jian-An Xian; Xiu-Xia Zhang; An-Li Wang (Fishes, 2022)
The objective of the present study was to investigate the effects of different doses of dietary Eucommia ulmoides leaf extract (ELE) on juvenile red claw crayfish (Cherax quadricarinatus). A total number of 720 red claw crayfish (initial body weight of 0.24 ± 0.01 g) were randomly assigned to six groups and fed diets containing 0 (Diet 1), 0.5 (Diet 2), 1 (Diet 3), 2 (Diet 4), 4 (Diet 5) and 10 (Diet 6) g dry weight (dw) ELE kg (dw)−1 diets for eight weeks and challenged with microcystin-LR stress. The results indicated that dietary supplementation with 1–2 g dw ELE kg (dw)−1 diet could significantly improve the weight gain rate (WGR) and specific growth rate (SGR) of crayfish. Muscle crude protein contents of crayfish fed Diet 2, Diet 3, and Diet 4 were significantly higher than those of the control group. Compared with the control group, dietary ELE could increase total antioxidant capacity (T-AOC), superoxide dismutase (SOD), glutathione peroxidase (GPx), acid phosphatase (ACP), alkaline phosphatase (AKP), and phenoloxidase (PO) activities and decrease malondialdehyde (MDA) level of crayfish. Dietary ELE significantly increased the relative expression levels of SOD, thioredoxin 1 (TRX1), GPx, selenium-dependent glutathione peroxidase (Se-GPx), cytochrome P450 (CYP450), anti-lipopolysaccharide factor (ALF) and C-type lysozyme (C-LZM) mRNA of crayfish compared with the control group during the feeding experiment. When subjected to MC-LR stress for 48 h, the mRNA expression levels of SOD, GPx, Se-GPx, glutathione-s-transferase 1 (GST1), ALF, hemocyanin (HEM), and C-LZM in the hepatopancreas could be improved to varying degrees compared with the Diet 1. Supplementation of 1–2 g dw ELE kg (dw)−1 diet could improve the survival rate (SR) of crayfish under MC-LR stress. These results indicated that dietary ELE (1–2 g dw ELE kg (dw)−1 diet) could improve the growth performance, muscle protein, and non-specific immune response and increase the SR of crayfish under MC-LR stress by regulating the mRNA expression levels of the immune- and antioxidant-related genes.

A new method for retrieving urban heat island intensity using GNSS-derived ZTD and atmospheric empirical model - Qimin He; Li Li; Dajun Lian; Hang Yu; Guodong Chen; Biqing Gao; Rui Wang; Kangming Song; Long Li (International Journal of Remote Sensing, 2022)

Assessing psychological factors on farmers' intention to apply organic manure: an application of extended theory of planned behavior - Jing Li; Rui Jiang; Xueyu Tang (Environment, Development and Sustainability, 2022)

Establishment and comprehensive analysis of a new human cell line (NK-NJ) with NK-cell characteristics established from extranodal natural killer cell lymphoma/leukemia - Jin-Hua Liang; Wei-Ting Wang; Kai-Xin Du; Tong-Yao Xing; Yan Wang; Hui Wang; Lu Liu; Rui Guo; Yang Shao; Junheng Liang; Yue Li; Hao-Rui Shen; et al. (Human Cell, 2022)

Highly efficient removal of hexavalent chromium by magnetic Fe–C composite from reed straw and electric furnace dust waste - Fu-Ping Wang; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Xi Zhang; Ai-Min Ji; Le-Le Kang; Rui Ji; Qing Yu; Di Gao; Xiao-Man Wang; Zhen Fang (Environmental Science and Pollution Research, 2022)

An efficient low-frequency artifact suppression method at excitation time for excitation amplitude imaging condition - Rui Wang; Deli Wang; Bin Hu; Weifeng Zhang; Jinju Zhou; Bowen Li (Acta Geophysica, 2022)

Multiple MicroRNAs are Involved in Regulating Peanut (Arachis hypogaea L.) Resistance to Sclerotium rolfsii at the Early Stage - Yongju Xu; Xiaojun Zhang; Rui Hou; Xiaohong Zhang; Shuang Li; Fuliang Yue; Xiangqiong Zhang; Xunlu Zhu (Tropical Plant Biology, 2022)

Efficacy and Safety of Recombinant Human Prourokinase in Acute Ischemic Stroke: A Phase IIa Randomized Clinical Trial - Haiqing Song; Yuan Wang; Qingfeng Ma; Huisheng Chen; Bo Liu; Yi Yang; Jianguo Zhu; Shigang Zhao; Xiaoping Jin; Yongqiu Li; Yanyong Wang; Runxiu Zhu; et al. (Translational Stroke Research, 2022)

Overexpression of α-Tubulin Gene of Sugarcane (Saccharum spp. hybrids), SoTUA, Enhances Tobacco Tolerance to Cold Stress - Jiao-Yun Chen; Bo Sun; Qaisar Khan; Li-Tao Yang; Bao-Qing Zhang; Yong-Xiu Xing; Yang-Rui Li (Sugar Tech, 2022)

CRISPR/dCas9 for hepatic fibrosis therapy: implications and challenges - Nianan Luo; Wenjun Zhong; Jiangbin Li; Jianguo Lu; Rui Dong (Molecular Biology Reports, 2022)

Changes in the gut microbiota of osteoporosis patients based on 16S rRNA gene sequencing: a systematic review and meta-analysis - Rui Huang; Pan Liu; Yiguang Bai; Jieqiong Huang; Rui Pan; Huihua Li; Yeping Su; Quan Zhou; Ruixin Ma; Shaohui Zong; Gaofeng Zeng (Journal of Zhejiang University-SCIENCE B, 2022)

Effects of Spartina alterniflora Invasion and Mangrove Restoration on Soil Microbial Functional Diversity - Yongni He; Genmei Lin; Xinyi Gao; Yiting Cao; Naxu Hu; Rui Li; Jianxiang Feng (Journal of Soil Science and Plant Nutrition, 2022)

The influence of weather and temperature on pedestrian walking characteristics on the zigzag bridge - Fan Dong; Xiaolian Li; Qimiao Xie; Rui Ye; Shuchao Cao (International Journal of Biometeorology, 2022)

Effects of Ran-GTP/importin β inhibition on the meiotic division of porcine oocytes - Yijing He; Jia Li; Lei Peng; Qiao Li; Yajie Chu; Qixin Lin; Jianjun Dai; Rong Rui; Shiqiang Ju (Histochemistry and Cell Biology, 2022)

Site-directed RNA editing by harnessing ADARs: advances and challenges - Ming Li; Cheng Yan; Yue Jiao; Yuqin Xu; Chen Bai; Rui Miao; Jiying Jiang; Jiao Liu (Functional & Integrative Genomics, 2022)

Temperature-dependent development and reproduction of Tarsonemus confusus (Acari: Tarsonemidae): an important pest mite of horticulture - Litao Li; Lichen Yu; Limin He; Xiong Zhao He; Rui Jiao; Changxin Xu (Experimental and Applied Acarology, 2022)

Removal performance and mechanisms of Pb(II) and Sb(V) from water by iron-doped phosphogypsum: single and coexisting systems - Xinyue Ma; Qiao Li; Rui Li; Wei Zhang; Xiuyun Sun; Jiansheng Li; Jinyou Shen; Weiqing Han (Environmental Science and Pollution Research, 2022)

Baicalin-berberine complex nanocrystals orally promote the co-absorption of two components - Ziwei Li; Yiting Liu; Jilin Wang; Xiaojiao Feng; Ebuka-Olisaemeka Nwafor; Ying Zhang; Rui Liu; Wenli Dang; Qingqing Zhang; Changxiang Yu; Jiaxin Pi; Zhidong Liu (Drug Delivery and Translational Research, 2022)

Effects of STAT3 Inhibitor BP-1-102 on The Proliferation, Invasiveness, Apoptosis and Neurosphere Formation of Glioma Cells in Vitro - Cheng-Chen Zhang; Ting Wu; Li Guan; Yu-Jue Wang; Rui-Qin Yao; Dian-Shuai Gao; Feng Li (Cell Biochemistry and Biophysics, 2022)

Effects of snow absence on available N pools and enzyme activities within soil aggregates in a spruce forest on the eastern Tibetan Plateau - Zhijie Li; Rüdiger Reichel; Zimin Li; Kaijun Yang; Li Zhang; Bo Tan; Rui Yin; Kerui Zhao; Zhenfeng Xu (Soil Ecology Letters, 2022)

Agricultural Applications and Potential Risks of Copper-Based Nanoagrochemicals in Crop Cultivation - Yanwanjing Liu; Weichen Zhao; Yongguang Yin; Muhammad Adeel; Noman Shakoor; Yuanbo Li; Zhiqiang Tan; Yukui Rui; Qinghua Zhang; Jingfu Liu; Baoshan Xing (Reviews of Environmental Contamination and Toxicology, 2022)

Long-term dietary restriction ameliorates ageing-related renal fibrosis in male mice by normalizing mitochondrial functions and autophagy - Chun-Hsien Chiang; Sin-Jin Li; Ting-Rui Zhang; Ching-Yi Chen (Biogerontology, 2022)

An improved bicubic imaging fitting algorithm for 3D radar detection target - Fan-Ruo Li; Feng Yang; Rui Yan; Qiao Xu; Yi-Jin Li; Hong-Jia Xing (Applied Geophysics, 2022)

Ferroptosis induced by the biocontrol agent Pythium oligandrum enhances soybean resistance to Phytophthora sojae - Yang Cheng; Huanxin Zhang; Wenyi Zhu; Qing Li; Rui Meng; Kun Yang; Ziqian Guo; Ying Zhai; Haijing Zhang; Rui Ji; Hao Peng; Daolong Dou; et al. (Environmental Microbiology, 2022)
Ferroptosis is a newly discovered form of cell death accompanied by iron accumulation and lipid peroxidation. Both biotic and abiotic stresses can induce ferroptosis in plant cells. In the case of plant interactions with pathogenic Phytophthora oomycetes, the roles of ferroptosis are still largely unknown. Here, we performed transcriptome analysis on soybean plants treated with the biocontrol agent Pythium oligandrum , a soilborne and non‐pathogenic oomycete capable of inducing plant resistance against Phytophthora sojae infection. Expression of homologous soybean genes involved in ferroptosis and resistance was reprogrammed upon P. oligandrum treatment. Typical hallmarks for characterizing ferroptosis were detected in soybean hypocotyl cells, including decreased glutathione (GSH) level, accumulation of ferric ions, and lipid peroxidation by reactive oxygen species (ROS). Meanwhile, ferroptosis‐like cell death was triggered by P. oligandrum to suppress P. sojae infection in soybean. Protection provided by P. oligandrum could be attenuated by the ferroptosis inhibitor ferrostatin‐1 (Fer‐1), suggesting the critical role of ferroptosis in soybean resistance against P. sojae . Taken together, these results demonstrate that ferroptosis is a P. oligandrum ‐inducible defence mechanism against oomycete infection in soybean.

Effects of coexposure to noise and mixture of toluene, ethylbenzene, xylene, and styrene (TEXS) on hearing loss in petrochemical workers of southern China - Yan Zhang; Yan Liu; Zongxin Li; Xin Liu; Qingfei Chen; Jingyao Qin; Qilong Liao; Rui Du; Qifei Deng; Yongmei Xiao; Xiumei Xing (Environmental Science and Pollution Research, 2022)

Environmental and economic benefits of substituting chemical potassium fertilizer with crop straw residues in China - Junhui Yin; Dongjia Li; Jingyao Yu; Xin Bai; Wenjing Cui; Rui Liu; Minghao Zhuang (Environmental Science and Pollution Research, 2022)

Nitrogen occurrence forms and bacterial community in sediment influenced by Bellamya purificata bioturbation - Yiyun Zhang; Yiran Hou; Rui Jia; Bing Li; Jian Zhu; Xianping Ge (Frontiers in Marine Science, 2022)
Endogenous water pollution and excessive nitrogen in ponds have always been prominent problems threatening aquaculture. To solve this problem, a 70-day indoor simulation experiment was conducted. The snail Bellamya purificata was stocked at four different densities: 0, 15, 30, and 60 individuals/tank, represented as CON (control), LD (low density), MD (medium density), and HD (high density), respectively, to investigate the effects of B. purificata on the nitrogen occurrence forms and bacterial communities in the sediment. At the end of the experiment, the nitrate concentration was significantly higher, while the total nitrogen content was significantly lower in the MD group than in the other three groups. Ammonia monooxygenase activity was significantly lower in the CON group than in the other three groups, and hydroxylamine oxidase activity was significantly higher in the HD group than in the other three groups. The CON and MD groups showed the highest and lowest values in nitrate reductase activity, respectively. The hydroxylamine reductase activity decreased significantly with increasing density. Through 16S ribosomal RNA (rRNA) high-throughput sequencing, significantly affected bacterial communities by B. purificata were found. Alpha diversity results showed that, a significantly lower Shannon index was observed in the MD group than in the other three groups. The LD and MD groups showed the highest and lowest Chao1 index values, respectively. Phyla Nitrospinae and family Nitrosomonadaceae were significantly enriched in the HD and MD groups, respectively. Redundancy analysis (RDA) indicated a significant correlation between differential bacterial taxa and TN content. Predicted functional analysis based on FAPROTAX (Functional annotation of prokaryotic taxa) database showed that functional groups aerobic ammonia oxidation and aerobic nitrite oxidation were significantly enriched in the MD group. Overall, B. purificata significantly altered the bacterial community composition, increased hydroxylamine oxidase and ammonia monooxygenase activities, enhanced the bacterial nitrification process, and promoted the transformation of total nitrogen to nitrate. Moreover, B. purificata stocked at 30 and 60 individuals/tank appeared to have a significant promotion effect on the bacterial community and nitrogen occurrence forms in the sediment. Hence, co-culturing B. purificata may be a feasible and effective ecological restoration method to alleviate excess nitrogen and reduce water eutrophication.

Enhancing extracellular electron transfer through selective enrichment of Geobacter with Fe@CN-modified carbon-based anode in microbial fuel cells - Xiao-Long Cheng; Qiang Xu; Qian-Wen Yang; Rui-Rui Tian; Biao Li; Su Yan; Xue-Ying Zhang; Jun Zhou; Xiao-Yu Yong (Environmental Science and Pollution Research, 2022)

Typhoon-Resistant Performance Assessment of Coastal Rural Residential Keel Brick Walls Reinforced with High Ductility Concrete - Qiang Li; Jun Zhang; Rui Wang; Jing Liu; Ping Li (Journal of Marine Science and Engineering, 2022)
The keel brick wall belongs to the rural residential exterior wall unique to the southeast coastal region of China. The wooden keel inside the wall and the external tie members can improve the stability of the whole wall. However, due to the age of construction, the wooden keel inside the existing residential keel brick walls has basically rotted and lost the tie with the external members, which seriously reduces the stability of the whole wall. Moreover, the collapse of keel brick walls caused by typhoons has become more and more frequent in recent years, seriously endangering the lives and properties of residents. Therefore, it is necessary to carry out reinforcement and repair for the existing residential buildings with keel brick walls. In this paper, the keel brick walls of rural houses in Ningbo area were taken as the research object, a framework for evaluating the performance of keel brick walls against typhoons was established, tests on the lateral force resistance of keel brick walls reinforced with high ductility concrete and mortar were carried out. With the help of typhoon full-track simulation and wind field simulation technology, the 600-year near-surface typhoon wind speeds affecting Ningbo area were obtained. A joint probability distribution model of multi-directional extreme wind speed was constructed using t-Copula function to determine the mixed wind climate of Ningbo area. The extreme wind loads that keel brick walls can withstand under four types of reinforcement were finally given. The results show that the high ductility concrete reinforcement has great advantages over mortar reinforcement and avoids brittle damage of the masonry structure. The keel brick walls reinforced with single-sided mortar can withstand wind loads of a 3-year return period, the keel brick walls reinforced with single-sided high ductile concrete can withstand extreme wind loads of a 110-year return period, while the keel brick walls reinforced with double-sided mortar as well as double-sided high ductile concrete can withstand extreme wind loads of well over a 110-year return period.

Comparison of horizontal wind observed by wind profiler radars with ERA5 reanalysis data in Anhui, China - Xueliang Deng; Dongyan He; Guangyuan Zhang; Song Zhu; Rui Dai; Xiaolong Jin; Wei Fu; Weiwei Shen; Jian Chen; Yuxiang Fan; Chunxuan Wei; Xin Li (Theoretical and Applied Climatology, 2022)

Knockdown of SOX9 alleviates tracheal fibrosis through the Wnt/β-catenin signaling pathway - Lei Gu; Anmao Li; Jing Lin; Yiling Gan; Chunyan He; Rui Xiao; Jiaxin Liao; Yishi Li; Shuliang Guo (Journal of Molecular Medicine, 2022)

Novel and sustainable carboxylation of terminal alkynes and CO2 to alkynyl carboxylic acids using triazolium ionic liquid-modified PMO-supported transition metal acetylacetonate as effective cooperative catalysts - Jing-Rui Li; Chen Chen; Xiao-Bing Liu; Yu-Lin Hu (Environmental Science and Pollution Research, 2022)

What is the short-term outlook for the EU’s natural gas demand? Individual differences and general trends based on monthly forecasts - Nu Li; Jianliang Wang; Rui Liu; Yan Zhong (Environmental Science and Pollution Research, 2022)

The inhibition of CFTR in the descended testis of SD rats with unilateral cryptorchidism induced by di-(2-ethylhexyl) phthalate (DEHP) - Xiangliang Tang; Dian Li; Tianxin Zhao; Shibo Zhu; Xiaofeng Gao; Rui Zhou; Fuming Deng; Wen Fu; Wei Jia; Guochang Liu (Environmental Science and Pollution Research, 2022)

Associations of exposure to lead and cadmium with risk of all-cause and cardiovascular disease mortality among patients with type 2 diabetes - Kai Zhu; Yuge Zhang; Qi Lu; Tingting Geng; Rui Li; Zhenzhen Wan; Xuena Zhang; Yujie Liu; Lin Li; Zixin Qiu; Meian He; Liegang Liu; et al. (Environmental Science and Pollution Research, 2022)

Characterization of a Hyaluronidase-Producing Bacillus sp. CQMU-D Isolated from Soil - Lu Wang; Qianqian Liu; Rui Hao; Jing Xiong; Junxing Li; Yanan Guo; Lu He; Zeng Tu (Current Microbiology, 2022)

Genistein Alleviates Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus by Activating the Sirt1/Nrf2 Pathway in High Salt-Induced Hypertension - Li-Gang Niu; Na Sun; Kai-Li Liu; Qing Su; Jie Qi; Li-Yan Fu; Guo-Rui Xin; Yu-Ming Kang (Cardiovascular Toxicology, 2022)

Risk Assessment and Source Identification of Arsenic in Surface Sediments from Caohai Lake, China - Ying Tang; Xinmin Liu; Rui Tian; Rui Li; Hang Li (Bulletin of Environmental Contamination and Toxicology, 2022)

Effects of rainfall and rocky desertification on soil erosion in karst area of Southwest China - Li-dong Pan; Rui Li; Dong-cai Shu; Li-na Zhao; Mei Chen; Jun Jing (Journal of Mountain Science, 2022)

A new process to further remove dissolved organic matter and disinfection by-product formation potential during drinking water treatment - Chongtian Lei; Yurong Chen; Aimin Li; Rui Gao; Ziang Zhang; Junxia Chen; Peng Shi; Qing Zhou; Yan Ma (Environmental Science and Pollution Research, 2022)

Two new triterpenoid glycosides from leaves of Cyclocarya paliurus - Huihui Sun; Hui Zhu; Jianping Wu; Yuyan Wang; Guihua Li; Yiqian Liu; Xiwen Chang; Saiyu Ou; Wenwen Zha; Huiyun Chen; Rui Gui; Xiaoai He; et al. (Natural Product Research, 2022)

Surfactin isoforms isolated from a mushroom derived Bacillus halotolerans DMG-7-2 - Guo-Feng Zhou; Lin Yang; Shu-Hua Zhang; Yi Wang; Yu Yang; Rui Xu; Xue Zhao; Dan Nie; Junjie Shan; Cheng-Bin Cui; Chang-Wei Li (Natural Product Research, 2022)

Monoterpenoid indole alkaloids with potential neuroprotective activities from the stems and leaves of Melodinus cochinchinensis - Yu-Jie Li; Juan Li; Lan Xie; Jun-Yu Zhou; Qiu-Xuan Li; Rui-Yuan Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2022)

Effects of two Mn-based nanomaterials on soybean antioxidant system and mineral element homeostasis - Yaqi Jiang; Pingfan Zhou; Tengtao Ma; Muhammad Adeel; Noman Shakoor; Yuanbo Li; Mingshu Li; Manlin Guo; Yukui Rui (Environmental Science and Pollution Research, 2022)

Evaluation of Port–Hinterland Synergy Level Considering Fixed Asset Allocation and Social Commodity Circulation under the “Dual Circulation” Development Pattern - Zhaohui Li; Yujin Huang; Fan Yang; Yi Li; Yan Fang; Rui Fu (Journal of Marine Science and Engineering, 2022)
“Port–hinterland synergy” means the development of port and hinterland should promote each other. The “dual circulation” development pattern indicates the requirement of exploring the domestic transportation demand and promoting the integration between ports and hinterlands. However, the current research on the synergy level between ports and hinterlands is not enough to meet the needs of constructing a “dual circulation” development pattern, and few studies have explored the influencing factors of port–hinterland synergy level directly, especially in the context of the new development pattern of “dual circulation”. After investigating the synergetic mechanism between ports and hinterlands, this study proposes to further consider the influence of fixed assets allocation and social commodity circulation on the synergy level under the “dual circulation” pattern. So, fixed asset investment and three different forms of commodity circulation activities are selected to represent the corresponding hinterland’s economic activities and added into the evaluation indices. To assess ports’ responsiveness to different kinds of transport demand, throughputs of each port are divided into those of domestic and foreign countries. Then this paper evaluates the level of port–hinterland synergy by the coupling synergy model, and the influence degree of these activities on the synergy level was studied with the partial least squares regression (PLS). The results show that there is heterogeneity in regional and port positioning in the port–hinterland synergy level, and that four selected economic activities’ improvement can enhance the port–hinterland synergy level. Among them, retail industry has the strongest positive effect, followed by tertiary industry, import and export trade, and fixed asset investment.

Hedgehog pathway is negatively regulated during the development of Drosophila melanogaster PheRS-m (Drosophila homologs gene of human FARS2) mutants - Lidangzhi Mo; Rui Li; Chunxia He; Qi Chen; Changwei Xu; Liangliang Shen; Kun Chen; Yuanming Wu (Human Cell, 2022)

Genome-wide identification of black pepper (Piper nigrum L.) Dof gene family and the differential gene screening in resistance to Phytophthora capsici - Fenju Zhang; Rui Fan; Lin Yan; Lisong Hu; Fan Su; Dewei Yang; Jing Li (Biologia, 2022)

Three new compounds from the leaves of Castanopsis tibetana Hance - Ya-Feng Wang; Rui-Jie He; Dian-Peng Li; Yong-Lin Huang (Natural Product Research, 2022)

U-net Models Based on Computed Tomography Perfusion Predict Tissue Outcome in Patients with Different Reperfusion Patterns - Yaode He; Zhongyu Luo; Ying Zhou; Rui Xue; Jiaping Li; Haitao Hu; Shenqiang Yan; Zhicai Chen; Jianan Wang; Min Lou (Translational Stroke Research, 2022)

Isolation and Analysis of Reverse Transcriptase of Ty1-copia-Like Retrotransposons in Sugarcane - Jun-Xian Liu; Jing Liu; Tai-Yi Yang; Li-Min Liu; Li-Hang Qiu; Yi-Jing Gao; Wei-Xing Duan; Jing-Chao Lei; Hong-Jian Liu; Rong-Hua Zhang; Wei-Zhong He; Song Li; et al. (Sugar Tech, 2022)

Human Urine-Derived Stem Cells Improve Partial Bladder Outlet Obstruction in Rats: Preliminary Data and microRNA-mRNA Expression Profile - Menjiang Tu; Rui Wang; Pei Zhu; Qingqing Wang; Bishao Sun; Keshi Lu; Jiawei Zhang; Weijie Xie; Huan Guo; Shulin Li; Yuqi Wu; Xiangwei Wang (Stem Cell Reviews and Reports, 2022)
Partial bladder outlet obstruction (pBOO) often results in bladder tissue inflammation and remodeling. As human urine-derived stem cells (USCs) have demonstrated therapeutic benefits, we used a rat model to investigate the effect of USCs on bladder function and explore the miRNA and gene expression profiles in bladder tissue using RNA sequencing. Eighteen rats were assigned to a sham surgery group, pBOO group, and pBOO+USC group (six biweekly treatments). Routine urodynamic monitoring, analysis of detrusor muscle strips, and pathophysiology assessments were conducted. Finally, altered miRNA and mRNA expression profiles of bladder tissue were examined using RNA sequencing and bioinformatics analysis. After USC treatment, elevated bladder compliance and maximal voiding pressure, declined end filling pressure and voided volume, and improved detrusor muscle contractility and carbachol sensitivity were found. Histology and TUNEL assay revealed reduced collagen deposition and muscle cell apoptosis in bladder tissue. The differential expression of eight miRNAs was reversed by USC treatment. Two large nodes (miR-142 and miR-9a) were identified in the miRNA-gene interaction network in the USC-treated group. The Kyoto Encyclopedia of Genes and Genomes analysis revealed enrichment of multiple significant pathways, including those involved in necroptosis and cytokine-cytokine receptor interactions. This is the first study to demonstrate the protective effect of USCs on bladder function and remodeling in pBOO rats. The miRNA and mRNA expression levels differed in the bladder of pBOO rats with and without USC treatment. Although the mechanism underlying these effects has not been fully elucidated, necroptosis and cytokine-cytokine receptor interaction-related pathways may be involved. Graphical abstract

SLAH1 is involved in the long-distance transport of Cl− from roots into shoots in the Cl−-tolerant xerophyte Pugionium cornutum under salt stress - Yan-Nong Cui; Xiao-Yu Li; Rui-Wen Liu; Zi-Hua He; Suo-Min Wang; Qing Ma (Plant and Soil, 2022)

Coastal vulnerability assessment based on multi-hazards and bio-geophysical parameters. case study - northwestern coastline of Guinea-Bissau - Namir Domingos Raimundo Lopes; Tianxin Li; Nametso Matomela; Rui Moutinho Sá (Natural Hazards, 2022)

Comparative analysis of mitochondrial genomes provides insights into the mechanisms underlying an S-type cytoplasmic male sterility (CMS) system in wheat (Triticum aestivum L.) - Rui Wang; Qingsong Ba; Lanlan Zhang; Weilun Wang; Pengfei Zhang; Guiping Li (Functional & Integrative Genomics, 2022)

Screening of microRNA and mRNA related to secondary hair follicle morphogenesis and development and functional analysis in cashmere goats - Fangzheng Shang; Yu Wang; Rong Ma; Youjun Rong; Min Wang; Zhihong Wu; Erhan Hai; Jianfeng Pan; Lili Liang; Zhiying Wang; Ruijun Wang; Rui Su; et al. (Functional & Integrative Genomics, 2022)
microRNA (miRNA) is a type of endogenous short-chain non-coding RNA with regulatory function found in eukaryotes, which is involved in the regulation of a variety of cellular and biological processes. However, the research on the development of cashmere goat secondary hair follicles is still relatively scarce. In this study, small RNA libraries and mRNA libraries of 45 days, 55 days, 65 days, and 75 days of fetal skin of cashmere goats were constructed, and the constructed libraries were sequenced using Illumina Hiseq4000, and the expression profiles of miRNA and mRNA in cashmere goat fetal skin were obtained. The differentially expressed miRNAs and mRNAs in six control groups were identified and the qRT-PCR experiment shows that the sequencing results are accurate. Sixty-six miRNAs related to secondary hair follicle development were screened, and used TargetScan and miRanda to predict 33 highly expressed miRNA target genes. At the same time, 664 mRNAs related to the development of secondary hair follicles were screened, and GO enrichment and KEGG pathway analysis were performed. It was found that some miRNA target genes were consistent with the screening results of mRNAs related to secondary hair follicle development and were enriched in Notch signaling pathway, TGF-β signaling pathway. Therefore, miR-145-5p-DLL4, miR-27b-3p-DLL4, miR-30e-5p-DLL4, miR-193b-3p-TGF-β1, miR-181b-5p-NOTCH2, and miR-103-3p-NOTCH2 regulatory network related to the development of secondary hair follicles were constructed and the results of dual-luciferase reporter gene assay indicated that there is a targeted relationship between chi-miR-30e-5p and DLL4, which will provide a basis for molecular mechanism of miRNA-mRNA in the development of the hair follicles in cashmere goats.

Effects of long-term sex steroid hormones (estradiol and testosterone)–supplemented feeds on the growth performance of Chinese tongue sole (Cynoglossus semilaevis) - Mengqian Zhang; Qian Yang; Rui Shi; Jialin Wang; Ziwei Zhang; Yingming Yang; Wenlong Li; Songlin Chen; Na Wang (Fish Physiology and Biochemistry, 2022)

Effect of winter feeding frequency on growth performance, biochemical blood parameters, oxidative stress, and appetite-related genes in Takifugu rubripes - Xiaoqiang Gao; Xinyi Wang; Xi Wang; Hongxu Li; Liang Xu; Yingying Fang; Shuquan Cao; Bin Huang; Haibin Chen; Rui Xing; Baoliang Liu (Fish Physiology and Biochemistry, 2022)

Clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in children in China - Wen Song; Qingwen Shan; Yue Qiu; Xianyao Lin; Chunhui Zhu; Zhiqiang Zhuo; Caihong Wang; Jianning Tong; Rui Li; Chaomin Wan; Yu Zhu; Minxia Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Invasive Salmonella infections result in a significant burden of disease including morbidity, mortality, and financial cost in many countries. Besides typhoid fever, the clinical impact of non-typhoid Salmonella infections is increasingly recognized with the improvement of laboratory detection capacity and techniques. A retrospective multicenter study was conducted to analyze the clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in hospitalized children in China during 2016–2018. A total of 130 children with invasive Salmonella infections were included with the median age of 12 months (range: 1–144 months). Seventy-nine percent of cases occurred between May and October. Pneumonia was the most common comorbidity in 33 (25.4%) patients. Meningitis and septic arthritis caused by nontyphoidal Salmonella (NTS) infections occurred in 12 (9.2%) patients and 5 (3.8%) patients. Patients < 12 months (OR: 16.04) and with septic shock (OR: 23.4), vomit (OR: 13.33), convulsion (OR: 15.86), C-reactive protein (CRP) ≥ 40 g/L (OR: 5.56), and a higher level of procalcitonin (PCT) (OR: 1.05) on admission were statistically associated to an increased risk of developing meningitis. Compared to 114 patients with NTS infections , 16 patients with typhoid fever presented with higher levels of CRP and PCT ( P < 0.05). The rates of resistance to ampicillin, sulfamethoxazole/trimethoprim, ciprofloxacin, and ceftriaxone among Salmonella Typhi and NTS isolates were 50% vs 57.3%, 9.1% vs 24.8%, 0% vs 11.2%, and 0% vs 9.9%, respectively. NTS has been the major cause of invasive Salmonella infections in Chinese children and can result in severe diseases. Antimicrobial resistance among NTS was more common.

Assessment of trace element contamination in the historical nesting grounds of green sea turtle (Chelonia mydas) in Hainan Island, China - Ting Zhang; Liu Lin; Deqin Li; Li Jian; Rui Li; Jichao Wang; Haitao Shi (Environmental Science and Pollution Research, 2022)

Associations of urinary polycyclic aromatic hydrocarbon metabolites and blood pressure with the mediating role of cytokines: A panel study among children - Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Huihua Yang; Jie Yu; Shuang Chen; Meng Li; Qin Fang; Xuefeng Lai; Liangle Yang; Rui Zhu; et al. (Environmental Science and Pollution Research, 2022)

Construction of a target MSNs drugcarrier loaded with siRNAGLI1 and siRNASMO aim at hedgehog signal pathway and the pharmacodynamic study of drug-carriers in the treatment of leukemia stem cells - Yuan Zhang; Rui Cai; HaiJun Li; Yu Duan; Yan Zhang; Wei Jing; ShaoGang Lv; Xi Chu; Zheng Cao; Lei Yang; Liang Ming (Drug Delivery and Translational Research, 2022)

Time-estimation process could cause the disappearence of readiness potential - Lipeng Zhang; Haikun Ren; Rui Zhang; Mingming Chen; Ruiqi Li; Li Shi; Dezhong Yao; Jinfeng Gao; Yuxia Hu (Cognitive Neurodynamics, 2022)

Protective Effect of Manganese on Apoptosis and Mitochondrial Function of Heat-Stressed Primary Chick Embryonic Myocardial Cells - Rui Wang; Zhaoguo Shi; Jinlu Li; Defu Tang; Shizhen Qin; Yanli Guo (Biological Trace Element Research, 2022)

Compounding soils to improve cropland quality: A study based on field experiments and model simulations in the loess hilly-gully region, China - Yun-xin Huang; Zheng-jia Liu; Yan-sui Liu; Yu-rui Li; Xue-qi Liu (Journal of Mountain Science, 2022)

A Label-Free Colorimetric Aptasensor Containing DNA Triplex Molecular Switch and AuNP Nanozyme for Highly Sensitive Detection of Saxitoxin - Xiaoyan Qi; Ling Li; Xiaochen Yan; Yinglin Zhao; Lele Wang; Rui Ma; Sai Wang; Xiangzhao Mao (Journal of Ocean University of China, 2022)

Direct Radiative Effects of Dust Aerosols over Northwest China Revealed by Satellite-Derived Aerosol Three-Dimensional Distribution - Rui Jia; Yuzhi Liu; Yan Li; Jun Li; Xiaolin Hu; Ronglu Gao; Yunfei Tian; Yanling Sun; Nannan Mu; Minfen Zhao (Journal of Meteorological Research, 2022)

Constructing a Ferroptosis-related Long Non-coding RNA Signature to Predict the Prognostic of Head and Neck Squamous Cell Carcinoma Patients by Bioinformatic Analysis - Rui Lu; Zhiyong Li; Shucheng Yin (Biochemical Genetics, 2022)
Ferroptosis is a novel discovered iron-dependent mode of regulated cell death (RCD) which characterized non-apoptosis. Researches have shown the effect of ferroptosis in the biological activities of tumors. But there is no relevant study showing the relationship between ferroptosis-related genes and head and neck squamous cell carcinoma (HNSCC). In this study, we paid attention to several ferroptosis-related lncRNAs in head and neck squamous cell carcinoma and its clinical features. HNSCC data were obtained from The Cancer Genome Atlas (TCGA) database. Ferroptosis-related lncRNAs were selected by the coexpression network. Then, we identified prognostic ferroptosis-related lncRNAs in HNSCC patients and constructed a ferroptosis-related lncRNAs signature by Lasso cox regression. Besides, GSEA analysis was performed to explore the functional enrichment of ferroptosis-related lncRNAs. Nine ferroptosis-related lncRNAs (AC004687.1, AL450992.2, AC010894.2, AL451085.2, AC104083.1, LIPE-AS1, AC108010.1, CTBP1-DT, and PTCSC2) were identified to have the independent prognostic value in HNSCC patients and the ferroptosis-related lncRNAs signature was constructed based on these nine genes. According to the risk score of the signature, the high-risk group had shorter overall survival (OS) compared with the low-risk group. Risk score showed to be an independent factor for the patients with HNSCC. Additionally, the nomogram was generated and the nine lncRNAs were mainly enriched in phagocytosis, metabolism, and chemokine signaling pathways. The ferroptosis-related lncRNA signature has effects on the prognostic prediction of patients with HNSCC which may serve as potential therapeutic targets for patients with HNSCC.

Meshless Surface Wind Speed Field Reconstruction Based on Machine Learning - Nian Liu; Zhongwei Yan; Xuan Tong; Jiang Jiang; Haochen Li; Jiangjiang Xia; Xiao Lou; Rui Ren; Yi Fang (Advances in Atmospheric Sciences, 2022)

The diminishing marginal contribution of R&D investment on green technological progress: a case study of China’s manufacturing industry - Xi Zhang; Rui Li; Jinglei Zhang (Environmental Science and Pollution Research, 2022)

Outdoor air pollution exposure and the risk of asthma and wheezing in the offspring - Lei Hua; Liangliang Ju; Hanbing Xu; Changlian Li; Shu Sun; Qi Zhang; Jiyu Cao; Rui Ding (Environmental Science and Pollution Research, 2022)

The complete paternally inherited mitochondrial genomes of three clam species in genus Macridiscus (Bivalvia: Veneridae): A TDRL model of dimer-mitogenome rearrangement of doubly uniparental inheritance - Rui Wang; Xuanzhao Li; Jiwei Qi (Frontiers in Marine Science, 2022)
One of the most striking exceptions to strict maternal inheritance of mitochondrial DNA (mtDNA) in the animal kingdom is a system called doubly uniparental inheritance (DUI), which exists in several bivalve species. DUI is characterized by the presence of two distinct sex-associated mitochondrial lineages: one transmitted through eggs (F-type mtDNA) and the other through sperm (M-type mtDNA). Presently, most known species exhibiting DUI belong to the freshwater bivalve order Unionoida. Other groups with species exhibiting DUI include the orders Mytiloida, Veneroida, and Nuculanoida. In Veneroida, the complete M-type mtDNA is available for two species. We report the presence of DUI in three species belonging to genus Macridiscus ( Macridiscus melanaegis , Macridiscus multifarious , and Macridiscus semicancellata ), in the order Veneroida, further obtaining their complete M-type mitogenomes. The M-type mitogenome sizes for M. melanaegis , M. multifarious , and M. semicancellata were 19,019 bp, 18,694 bp, and 18,726 bp, respectively, and the mean nucleotide difference between M-type and F-type mitogenomes was 21–23%. We compared the M-type and F-type mitogenomes and found that they show roughly the same genome features, except for gene order. In phylogenetic analyses of Veneroida, a “gender-joining” pattern was revealed within Macridiscus , similar to the pattern of “partial” Mytilus complex (except Unionida). This new insight provides novel evidence supporting the theory that Veneroida and Mytiloida have a more similar DUI pattern than Unionida. A large-scale rearrangement between the sex-linked mitogenomes of the three Macridiscus species was reported. From the observed rearrangement patterns, gene rearrangement between the two sex-linked mitogenomes could be explained by the tandem duplication and random loss (TDRL) model of dimer-mitogenome. This is the first report of heterogeneous genomes with two types of large-scale arrangements in the same organism, and may be contribute significantly to the study of mitochondrial recombination mechanisms.

Fosthiazate exposure induces oxidative stress, nerve damage, and reproductive disorders in nontarget nematodes - Shiling Liu; Qiqi Wu; Yanru Zhong; Zongzhe He; Zhen Wang; Rui Li; Minghua Wang (Environmental Science and Pollution Research, 2022)

Changes in amino acid and fatty acid composition during early development in cobia (Rachycentron canadum) - Jian-sheng Huang; Rong-xin Li; Rui-tao Xie; You-ming Chen; Jian-dong Zhang; Eric Amenyogbe; Gang Chen (Frontiers in Marine Science, 2022)
An estimation of the utilization of endogenous nutrients from the yolk sac that occurs during embryonic and early larval development can be a valuable approach to studying the nutritional requirements of fish larvae. In this study, fertilized eggs, embryos (before the membrane, 24 hours after fertilization), newly-hatched larvae (0-d-old), and open-mouthed larvae (3-day-old, unfed rotifers) samples of cobia ( Rachycentron canadum ) were collected to determine the amino acid and fatty acid profiles. Crude protein composition varies significantly for cobia during the different stages of development. The total amino acids, except for lysine(Lys), histidine (His), methionine(Met), serine(Ser), and glycine(Gly), had no significant change in the early development stage ( P > 0.05); the content of other six essential amino acids (EAA) and six non-essential amino acids (NEAA) was consistent with the changing trend of total essential amino acid. From hatching newly hatched larvae to open-mouthed larvae, except for Leu, Phe and Ser, decreased significantly ( P <0.05). From the utilization rate of FAA, the utilization rate of Lys and Leu was the highest (60.26%) and (52.21%) in the embryonic and endogenous nutritional stages, respectively. The water content of the open-mouthed larvae of cobia was significantly higher than that of the fertilized eggs, embryos, and newly hatched larvae ( P < 0.05). Three kinds of saturated fatty acids (SFA), five kinds of monounsaturated fatty acids (MUFA), and eight kinds of polyunsaturated fatty acids (PUFA) were detected in the dry samples of each developmental stage. Based on these results, juvenile cobia can thrive with a wide range of crude protein concentrations. Further refinement of commercial cobia production feeds would have beneficial consequences for economic and environmental concerns due to the positive impacts of optimizing the protein component as well as the ability to maintain the rapid growth rates. The results show that the larval development of cobia needs to consume large amounts of n3PUFA (especially DHA and EPA) to improve the larvae’s survival rate. Research methods will always have limitations when evaluating the relationship between early life nutrition interventions and well-being outcomes later in life. This study provides essential information regarding cobia larvae’s fatty acid requirements.

Can green finance promote urban green development? Evidence from green finance reform and innovation pilot zone in China - Hongfeng Zhang; Yixiang Wang; Rui Li; Hongyun Si; Wei Liu (Environmental Science and Pollution Research, 2022)

Treating performance of a commercial-scale constructed wetland system for aquaculture effluents from intensive inland Micropterus salmoides farm - Bing Li; Rui Jia; Yiran Hou; Jian Zhu (Frontiers in Marine Science, 2022)
In intensive inland fish farming, discharge of untreated effluents adversely affects adjacent water bodies and causes water pollution. Thus, it is highly necessary to treat the effluents from inland fish farm. In this study, we built a commercial-scale integrated constructed wetland (CW) system with vertical subsurface flow, and monitored the purifying effect. During fish farming and discharge of effluents periods, the water samples were collected to detected the total nitrogen (TN), total phosphorus (TP), ammonia nitrogen (NH 4 + -N), nitrate nitrogen (NO 3 - -N), nitrite nitrogen (NO 2 - -N) and chemical oxygen demand (COD Mn ). Results showed that the system was stable and significantly improved water quality from fish pond. During the fish farming period, the removal efficiency for TN, TP, NH 4 + -N, NO 3 - -N, NO 2 - -N, and COD was 24.93–43.72%, 61.92–72.18%, 56.29–68.63%, 56.66–64.81%, 56.42–64.19% and 28.37–42.79%, respectively. Similarly, these parameters were also markedly decreased by the integrated CW system during sewage discharge period, and the average total removal rate for TN, TP, NH 4 + -N, NO 3 - -N, NO 2 - -N, and COD was 50.24%, 64.48%, 61.36%, 62.65%, 56.16% and 37.32%, respectively. It was worth noting that three key parameters for effluents detection TN, TP and COD values were below the threshold values of water quality of Class II in freshwater sewage discharge standard of China (SCT9101-2007). In conclusion, this study evidently demonstrated that application of CW system was an environmental sustainable sewage treatment strategy in intensive inland fish farming.

Aluminum-activated Malate Transporter 12 is involved in restricting root-to-shoot Cl− transport in Arabidopsis under Cl−-salt stress - Rui-Wen Liu; Jian-Zhen Yuan; Xiao-Yu Li; Yan-Nong Cui; Mei-Mei Cai; Zi-Hua He; Qing Ma (Plant and Soil, 2022)

Wnt Signaling Pathways: A Role in Pain Processing - Yiting Tang; Yupeng Chen; Rui Liu; Weidong Li; Baojin Hua; Yanju Bao (NeuroMolecular Medicine, 2022)
The wingless-related integration site (Wnt) signaling pathway plays an essential role in embryonic development and nervous system regulation. It is critically involved in multiple types of neuropathic pain (NP), such as HIV-related NP, cancer pain, diabetic neuralgia, multiple sclerosis-related NP, endometriosis pain, and other painful diseases. Wnt signaling is also implicated in the pain induced by sciatic nerve compression injury and selective spinal nerve ligation. Thus, the Wnt signaling pathway may be a potential therapeutic target for NP.

An improved DebrisInterMixingFoam for debris flow simulation: numerical investigation and application - Rui Li; Yuliang Teng (Natural Hazards, 2022)

Identification of Ferroptotic Genes in Spinal Cord Injury at Different Time Points: Bioinformatics and Experimental Validation - Yu Kang; Qiangwei Li; Rui Zhu; Shuang Li; Xin Xu; Xuanming Shi; Zongsheng Yin (Molecular Neurobiology, 2022)

Triphenylpyrazoline ketone chlorophenols as potential candidate compounds against Parkinson’s disease: design, synthesis, and biological evaluation - Ning Ning Cheng; Le Hua Zhang; Rui Ge; Xiu E. Feng; Qing Shan Li (Medicinal Chemistry Research, 2022)

Sparse principal component analysis based on genome network for correcting cell type heterogeneity in epigenome-wide association studies - Rui Miao; Qi Dang; Jie Cai; Hai-Hui Huang; Sheng-Li Xie; Yong Liang (Medical & Biological Engineering & Computing, 2022)

Dynamic mechanical behavior of coral rock subjected to high strain rate loading - Houzhen Wei; Linjian Ma; Jiawen Wu; Jin Yu; Zeng Li; Rui Xu (Marine Geophysical Research, 2022)

Orbit determination, clock estimation and performance evaluation of BDS-3 PPP-B2b service - Chengpan Tang; Xiaogong Hu; Jinping Chen; Li Liu; Shanshi Zhou; Rui Guo; Xiaojie Li; Feng He; Jinhuo Liu; Jianhua Yang (Journal of Geodesy, 2022)

MicroRNA alteration in cerebrospinal fluid from comatose patients with traumatic brain injury after right median nerve stimulation - Ying Jia; Yi-fan He; Ye Tian; Yuan-zhi Wang; Rui-ting Zhao; Xiao-chun Li; Jian Sun; Ying-sheng Wei; Shuo An; Heng-jie Yuan; Chun-xiao Wan; Rong-cai Jiang (Experimental Brain Research, 2022)

Association between ambient air pollution exposure during pregnancy and gestational diabetes mellitus: a meta-analysis of cohort studies - Xinyu Zhou; Changlian Li; Han Cheng; Junyi Xie; Feng Li; Lishan Wang; Rui Ding (Environmental Science and Pollution Research, 2022)

Effects of perfluorooctanoic acid (PFOA) on activated sludge microbial community under aerobic and anaerobic conditions - Duanyi Huang; Rui Xu; Xiaoxu Sun; Yongbin Li; Enzong Xiao; Zhimin Xu; Qi Wang; Pin Gao; Zhaohui Yang; Hanzhi Lin; Weimin Sun (Environmental Science and Pollution Research, 2022)

Human health risk assessment of heavy metals from PM2.5 in China’s 29 provincial capital cities - Li Li; Rui Meng; Yalin Lei; Sanmang Wu; Yong Jiang (Environmental Science and Pollution Research, 2022)

Hydrogeochemical characteristics and gradual changes of groundwater in the Baiquan karst spring region, northern China - Rui Wang; Xiaohan Li; Aihua Wei (Carbonates and Evaporites, 2022)

Parameter estimation of sediment in the Yellow River based on the porous medium acoustic theory - Chang-Zheng Li; Chao-Yang Song; Rui Wang (Applied Geophysics, 2022)

Spatiotemporal Variations of Microwave Land Surface Emissivity (MLSE) over China Derived from Four-Year Recalibrated Fengyun 3B MWRI Data - Rui Li; Jiheng Hu; Shengli Wu; Peng Zhang; Husi Letu; Yu Wang; Xuewen Wang; Yuyun Fu; Renjun Zhou; Ling Sun (Advances in Atmospheric Sciences, 2022)

A Realistic and Integrated Model for Evaluating Offshore Oil Development - Rui Qiu; Zhuochao Li; Qin Zhang; Xin Yao; Shuyi Xie; Qi Liao; Bohong Wang (Journal of Marine Science and Engineering, 2022)
With the rising consumption of oil resources, major oil companies around the world have increasingly engaged in offshore oil exploration and development, and offshore oil resources have accounted for an increasing proportion. Offshore oil engineering projects are capital intensive, and the development of offshore oil fields faces a tough battle, especially in a period of low oil prices. Thus, a comprehensive evaluation model is highly needed to help assess economic benefits and provide meaningful and valuable information for operators and investors to make sensible decisions. This study firstly proposed a realistic and integrated evaluation model for offshore oil development based on actual historical project data. This evaluation model incorporated modules from the underwater system to the platform system and processes from oil reservoir extraction to oil, gas and water treatment. The uncertain parameters in the evaluation process are dealt with by sensitivity analysis and Monte Carlo simulation. The proposed model is applied to a typical offshore oil development project in Bohai Bay, China. The results reveal that the recovery factor and oil price have the greatest impact on the economic benefits. In the case of deterministic analysis, the breakeven oil price of the project is 40.59 USD/bbl. After considering the uncertainty of project parameters, the higher the oil price, the greater the probability of NPV > 0. When the oil price is higher than 70 USD/bbl, even with uncertain project parameters, the probability of NPV > 0 can still be as high as 97.39%.

Effects of Alkalinity on the Antioxidant Capacity, Nonspecific Immune Response and Tissue Structure of Chinese Mitten Crab Eriocheir sinensis - Mingshuai Li; Shihui Wang; Zhigang Zhao; Liang Luo; Rui Zhang; Kun Guo; Lanlan Zhang; Yuhong Yang (Fishes, 2022)
The effects of various levels of alkalinity stress (0, 18.25, 35.41, 52.53 and 69.74 mmol/L) in Chinese mitten crab (Eriocheir sinensis) were investigated by means of measuring hepatopancreas antioxidant system and serum nonspecific immune system-related indices at 0, 12, 24, 48 and 96 h, hepatopancreas tissue structure at 96 h. The activities of superoxide dismutase (SOD), catalase (CAT), glutathione (GSH) and aspartate aminotransferase (AST) in each concentration group generally showed a trend of a first increasing and then decreasing during the 96-h stress process (p 0.05). The activities of CAT, GSH and AST in all treatment reached peak values at 24–48 h. At 96 h of alkalinity stress, the activities of GSH, alanine aminotransferase (ALT), acid phosphatise (ACP) and alkaline phosphatise (AKP) in the 18.25 mmol/L group were not significantly different with the control group (p > 0.05). The activities of SOD and CAT in the 52.53 and 69.74 mmol/L treatment were significantly lower than those in the control group (p

YOLO-Rip: A modified lightweight network for Rip currents detection - Daoheng Zhu; Rui Qi; Pengpeng Hu; Qianxin Su; Xue Qin; Zhiqiang Li (Frontiers in Marine Science, 2022)
Rip currents form on beaches worldwide and pose a potential safety hazard for beach visitors. Therefore, effectively identifying rip currents from beach scenes and providing real-time alerts to beach managers and beachgoers is crucial. In this study, the YOLO-Rip model was proposed to detect rip current targets based on current popular deep learning techniques. First, based on the characteristics of a large target size in rip current images, the neck region in the YOLOv5s model was streamlined. The 80 × 80 feature map branches suitable for detecting small targets were removed to reduce the number of parameters, decrease the complexity of the model, and improve the real-time detection performance. Subsequently, we proposed adding a joint dilated convolutional (JDC) module to the lateral connection of the feature pyramid network (FPN) to expand the perceptual field, improve feature information utilization, and reduce the number of parameters, while keeping the model compact. Finally, the SimAM module, which is a parametric-free attention mechanism, was added to optimize the target detection accuracy. Several mainstream neural network models have been used to train self-built rip current image datasets. The experimental results show that (i) the detection results from different models using the same dataset vary greatly and (ii) compared with YOLOv5s, YOLO-Rip increased the mAP value by approximately 4% (to 92.15%), frame rate by 2.18 frames per second, and the model size by only 0.46 MB. The modified model improved the detection accuracy while keeping the model streamlined, indicating its efficiency and accuracy in the detection of rip currents.

Research on PEMS Test Data Processing Method and Cold Start Emission Evaluation Method of Heavy-Duty Diesel Vehicles - Gangzhi Tang; Shuaibin Wang; Rui Wang; Baocheng Du; Yu Liu; Gang Tian; Linyao Ran; Gan Xiang; Huang Li (Water, Air, & Soil Pollution, 2022)

Magnetic Resonance Imaging Markers of Cerebral Small Vessel Disease in Adults with Moyamoya Disease - Haogeng Sun; Wanjiang Li; Chao Xia; Yutao Ren; Lu Ma; Anqi Xiao; Chao You; Xiaoyu Wang; Rui Tian; Yi Liu (Translational Stroke Research, 2022)

An alanine to valine mutation of glutamyl-tRNA reductase enhances 5-aminolevulinic acid synthesis in rice - Meng Jiang; Shang Dai; Yun-Chao Zheng; Rui-Qing Li; Yuan-Yuan Tan; Gang Pan; Ian Max Møller; Shi-Yong Song; Jian-Zhong Huang; Qing-Yao Shu (Theoretical and Applied Genetics, 2022)

Proteome Based Comparative Investigation of a High Sucrose Sugarcane Mutant in Contrast to the Low Sucrose Mother Variety by Using TMT Quantitative Proteomics - Qaisar Khan; Ying Qin; Dao-Jun Guo; Zhen Lu; Xian-Qiu Xie; Li-Tao Yang; Qiang Liang; Xiu-Peng Song; Yong-Xiu Xing; Yang-Rui Li (Sugar Tech, 2022)

Occurrence and distribution of geminiviruses in China - Fangfang Li; Rui Qiao; Zhanqi Wang; Xiuling Yang; Xueping Zhou (Science China Life Sciences, 2022)

Correction to: Methylation and expression quantitative trait locus rs6296 in the HTR1B gene is associated with susceptibility to opioid use disorder - Yunxiao Li; Ye Lu; Qiaoli Xie; Xiaofeng Zeng; Rui Zhang; Wei Dang; Yongsheng Zhu; Jianbo Zhang (Psychopharmacology, 2022)

Alterations in gut microbiota affect behavioral and inflammatory responses to methamphetamine in mice - Simin Lai; Jing Wang; Biao Wang; Rui Wang; Guodong Li; Yuwei Jia; Teng Chen; Yanjiong Chen (Psychopharmacology, 2022)

Methylation and expression quantitative trait locus rs6296 in the HTR1B gene is associated with susceptibility to opioid use disorder - Yunxiao Li; Ye Lu; Qiaoli Xie; Xiaofeng Zeng; Rui Zhang; Wei Dang; Yongsheng Zhu; Jianbo Zhang (Psychopharmacology, 2022)

Canagliflozin mitigates ferroptosis and ameliorates heart failure in rats with preserved ejection fraction - Sai Ma; Li-Li He; Guo-Rui Zhang; Qing-Juan Zuo; Zhong-Li Wang; Jian-Long Zhai; Ting-Ting Zhang; Yan Wang; Hui-Juan Ma; Yi-Fang Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)
Recently, hypoglycemic drugs belonging to sodium-glucose cotransporter 2 inhibitors (SGLT2i) have generated significant interest due to their clear cardiovascular benefits for heart failure with preserved ejection fraction (HFpEF) since there are no effective drugs that may improve clinical outcomes for these patients over a prolonged period. But, the underlying mechanisms remain unclear, particularly its effects on ferroptosis, a newly defined mechanism of iron-dependent non-apoptotic cell death during heart failure (HF). Here, with proteomics, we demonstrated that ferroptosis might be a key mechanism in a rat model of high-salt diet-induced HFpEF, characterized by iron overloading and lipid peroxidation, which was blocked following treatment with canagliflozin. Data are available via ProteomeXchange with identifier PXD029031. The ferroptosis was evaluated with the levels of acyl-CoA synthetase long-chain family member 4, glutathione peroxidase 4, ferritin heavy chain 1, transferrin receptor, Ferroportin 1, iron, glutathione, malondialdehyde, and 4-hydroxy-trans-2-nonenal. These findings highlight the fact that targeting ferroptosis may serve as a cardioprotective strategy for HFpEF prevention and suggest that canagliflozin may exert its cardiovascular benefits partly via its mitigation of ferroptosis.

Modeling-Based Multiscale Deep Prospectivity Mapping: A Case Study of the Haoyaoerhudong Gold Deposit, Inner Mongolia, China - Nan Li; Rui Cao; HuiShou Ye; Qiang Li; Yitian Wang; Xiping Lv; Na Guo; Yuanxiang Su; Jianrui Hao; Shitao Yin; Wenkai Chu (Natural Resources Research, 2022)

miR-517b-3p promotes the progression of portal vein tumor thrombus via activating Wnt/β-catenin signaling pathway in hepatocellular carcinoma - Rui-Sheng Ke; Kun-Zhai Huang; De-sheng Bao; Jing-Rui Yang; Hua-xiang Wang; Li-Zhi Lv; Yi Jiang; Zhao-Hui Liu; Fu-Xing Zhang (Molecular Biology Reports, 2022)

Activation of the TREK-1 Potassium Channel Improved Cognitive Deficits in a Mouse Model of Alzheimer’s Disease by Modulating Glutamate Metabolism - Fang Li; Shu-ning Zhou; Xin Zeng; Zhen Li; Rui Yang; Xue-xi Wang; Bin Meng; Wei-lin Pei; Li Lu (Molecular Neurobiology, 2022)

RNAi-Based Transcriptome Suggests Candidate Genes Regulated by ZxNHX1 to Affect The Salt Tolerance of Zygophyllum xanthoxylum - Hai-Shuang Liu; Xiao-Nong Guo; Wei-Wei Chai; Rui-Xin Zhang; Pei-Qin Li; Cui-Min Ma; Qing Ma; Suo-Min Wang (Journal of Plant Growth Regulation, 2022)

Comparative low lethal effects of three insecticides on demographical traits and enzyme activity of the Spodoptera exigua (Hübner) - Muhammad Hafeez; Farman Ullah; Muhammad Musa Khan; Zhangqian Wang; Hina Gul; Xiaowei Li; Jun Huang; Junaid Ali Siddiqui; Muhammad Qasim; Rui-Long Wang; Muhammad Imran; Mohammed A. Assiri; et al. (Environmental Science and Pollution Research, 2022)

Preparing porous Cu/Pd electrode on nickel foam using hydrogen bubbles dynamic template for high-efficiency and high-stability removal of nitrate from water - Jialu Shi; Ya Gao; Daoru Liu; Zhanhui Shen; Jing Fan; Yating Yu; Meihui Bao; Panpan Li; Rui Yao (Environmental Science and Pollution Research, 2022)

Fractal morphology facilitates Bacillus subtilis biofilm growth - Jiankun Wang; Xianyong Li; Rui Kong; Jin Wu; Xiaoling Wang (Environmental Science and Pollution Research, 2022)

Influence of different inoculation densities of black soldier fly larvae (Hermetia illucens) on heavy metal immobilization in swine manure - Dongmei Jiang; Kunhong Jiang; Rui Li; Liangbin Zhao; Zile Liu; Bangjie Xiong; Du Jin; Xiaoxia Hao; Li Zhu; Bo Kang; Lin Bai (Environmental Science and Pollution Research, 2022)

Detection and typing of dengue virus by one-step RT-PCR-based high-resolution melting assay - Rui Tian; Hao Yan; Yang Jiang; Aiping Wu; Ling Li; Zhangnv Yang; Kuangming Yu (Virus Genes, 2022)

Linkages among the functional traits, insect visitation rate and seed set of Gentiana taxa on the Tibetan Plateau - Wen-fei Dai; Rui Gao; Meng-ying He; Yu-lian Yang; Fang-lan Li; Jun-peng Mu (Journal of Mountain Science, 2022)

Molecular Characterization, Expression Pattern and Transcriptional Regulation of Figla During Gonad Development in Japanese Founder (Paralichthys olivaceus) - Jiangbo Qu; Rui Li; Yuxiang Liu; Minmin Sun; Weijie Yan; Jinxiang Liu; Xubo Wang; Quanqi Zhang (Journal of Ocean University of China, 2022)

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

Longitalea arenae gen. nov., sp. nov. and Longitalea luteola sp. nov., two new members of the family Chitinophagaceae isolated from desert soil - Shuai Li; Lei Dong; Jia-Rui Han; Guo-Yuan Shi; Chun-Yan Lu; Lu Xu; Wen-Hui Lian; Dalal Hussien M. Alkhalifah; Wael N. Hozzein; Wen-Jun Li (Archives of Microbiology, 2022)

Petrogenesis of the Lunar volcanic glasses and Mg-suite: constraints on a post-magma-ocean cumulate overturn - Rui Li; Wei Du; Jing Yang (Acta Geochimica, 2022)

Characteristics of summer cloud precipitation along latitude 30°N in East Asia derived from Tropical Rainfall Measuring Mission Precipitation Radar and Visible and Infrared Scanner measurements - Mengxiao Wang; Yunfei Fu; Chun Zhao; Lei Zhong; Rui Li; Dongyong Wang; Xuexing Qiu; Shengnan Zhou (International Journal of Climatology, 2022)
There has been little systematic analysis of the influence of the three‐step staircase topography on the characteristics of precipitation along latitude 30°N in East Asia. After the distribution of atmospheric climate states over East Asia was analysed, in this study, the climatological characteristics of summer convective and stratiform precipitation on horizontal distribution, vertical structure, and diurnal variation in East Asia were investigated by using a merged dataset derived from the measurements of the Tropical Rainfall Measuring Mission Precipitation Radar and Visible and Infrared Scanner from 1998 to 2012 reanalysis datasets. Results indicate that the rain frequency, the mean rain rate, and the maximum echo reflectivity factor show clear differences among the three‐step staircase topography, especially between the first staircase and its eastern region. There are small changes in the echo‐top height, the cloud‐top height, the maximum echo reflectivity factor and its corresponding height from the East China Sea westwards to the eastern part of the first staircase, passing the third staircase and the second staircase along 30°N. However, the rain rate decreased obviously twice westwards along this latitude, which responds to aerosol indirect effect and humidity effect, respectively. The diurnal variation of the convective precipitation reflectivity factor indicated that the development of convection in the eastern part of the first staircase gets at the maximum from the early afternoon to sunset, whereas the strongest echo reflectivity factor of precipitation in the second and third staircases including the East China Sea appears in the early morning, which is consistent with the diurnal variations of the atmospheric circulation.

Machine learning for microalgae detection and utilization - Hongwei Ning; Rui Li; Teng Zhou (Frontiers in Marine Science, 2022)
Microalgae are essential parts of marine ecology, and they play a key role in species balance. Microalgae also have significant economic value. However, microalgae are too tiny, and there are many different kinds of microalgae in a single drop of seawater. It is challenging to identify microalgae species and monitor microalgae changes. Machine learning techniques have achieved massive success in object recognition and classification, and have attracted a wide range of attention. Many researchers have introduced machine learning algorithms into microalgae applications, and similarly significant effects are gained. The paper summarizes recent advances based on various machine learning algorithms in microalgae applications, such as microalgae classification, bioenergy generation from microalgae, environment purification with microalgae, and microalgae growth monitor. Finally, we prospect development of machine learning algorithms in microalgae treatment in the future.

Electrospun nanofibers food packaging: trends and applications in food systems - Dur E. Sameen; Saeed Ahmed; Rui Lu; Rui Li; Jianwu Dai; Wen Qin; Qing Zhang; Suqing Li; Yaowen Liu (Critical Reviews in Food Science and Nutrition, 2022)

Spatial-temporal distribution and tectonic setting of Mesozoic W-mineralized granitoids in the Xing-Meng Orogenic Belt, NE China - Wei Xie; Qing-Dong Zeng; Rui-Liang Wang; Jin-Jian Wu; Zhe-Ming Zhang; Feng-Chun Li; Zhuang Zhang (International Geology Review, 2022)

Development of Solid-State Anaerobic Digestion and Aerobic Composting Hybrid Processes for Organic Solid Waste Treatment and Resource Recovery: a Review - Chuanren Qi; Rongrong Yin; Xingzu Gao; Jie Chen; Rui Wang; Zhicheng Xu; Wenhai Luo; Guoxue Li; Yangyang Li (Current Pollution Reports, 2022)

Temporal Dynamics in Energy Fluxes and Trophic Structure of a Portunus trituberculatus Polyculture Ecosystem During Different Culture Periods - Jie Feng; Xiang-Li Tian; Shuang-Lin Dong; Rui-Peng He; Kai Zhang; Dong-Xu Zhang; Qing-Qi Zhang (Frontiers in Marine Science, 2022)
Swimming crab ( Portunus trituberculatus ) are an important aquaculture species in eastern coastal areas of China. To improve the understanding of P. trituberculatus culture ecosystem functioning, the dynamics of energy flow and trophic structure of a P. trituberculatus polyculture system (co-culture with white shrimp Litopenaeus vannamei and short-necked clam Ruditapes philippinarum ) were investigated in this study. Three Ecopath models representing the early, middle, and late culture periods of a P. trituberculatus polyculture ecosystem, respectively, were constructed to compare ecosystem traits at different culture periods. The results demonstrated that detritus was the main energy source in this polyculture ecosystem, and most of the total system throughput occurred at trophic levels I and II. Artificial food input and consumption by the culture organisms increased from early to middle and late periods, which produced marked impacts on biomass structure and primary production. R. philippinarum was considered to have a dominant influence on phytoplankton community dynamics which changed from nano- to pico-phytoplankton predominance, from the middle to the late period. Considering the low utilization efficiency of pico-phytoplankton production, large amounts of detritus accumulated in the sediment in the late period, which may constitute a potential risk for the ecosystem. Ecological network analyses indicated that the total energy flow and level of system organization increased from the early to the middle and late periods, whereas food web complexity and system resilience decreased from early to middle and late periods, which may indicate a trend of decreasing ecosystem stability. The system may be further optimized by increased stocking density of R. philippinarum and by introducing macro-algae at a suitable biomass to increase ecosystem stability, energy utilization efficiency, and aquaculture production.

Oyster and Barnacle Recruitment Dynamics on and Near a Natural Reef in China: Implications for Oyster Reef Restoration - Wei Jiang; Wen-Jing Shi; Nan-Nan Li; Rui-Liang Fan; Wen-Kao Zhang; Wei-Min Quan (Frontiers in Marine Science, 2022)
Oysters and barnacles are dominant inhabitants of natural and restored oyster reefs around the world, and high areal coverage of barnacles at natural or restored reefs commonly decreases substrate accessibility for oyster settlement. The overall understanding of oyster and barnacle recruitment dynamics provides invaluable information on site selection and strategies employed for oyster reef restoration. This study documented the temporal and spatial patterns of oyster and barnacle recruitment on and near the largest natural intertidal oyster reef (Liyashan) in China during 2019–2020. The oyster Crassostrea sikamea recruitment appeared as a continuous process from June through late November or early December, with the peak in August. Greater recruits of oyster spat occurred on the sheltered inshore at the upstream of the natural oyster reef than on the reef and the nearby open coast ( p < 0.05). The barnacle recruitment extended from spring to early winter, with mid-spring and mid-summer peaks. Conversely, higher barnacle recruitment appeared on the natural oyster reef and the nearby open coast than on the sheltered inshore. Across all the monitoring sites, the cumulative recruits of oysters in each of 2019 and 2020 was negatively correlated with those of barnacles ( p < 0.05). The inshore sites (SH1 and SH2) with high oyster recruitment and low barnacle recruitment should be recognized as the natural spatfall sites for the natural oyster reef restoration. The separation in the recruitment peak between the oyster and the barnacle indicated that August was the most favorable window for capturing oyster spat through substratum addition to the water around the natural reef.

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Influences of Coal Seam Heterogeneity on Hydraulic Fracture Geometry: An In Situ Observation Perspective - Rui Li; Shengwei Wang; Guofu Li; Jiacheng Wang (Rock Mechanics and Rock Engineering, 2022)

Belowground processes and sustainability in agroecosystems with intercropping - Rui-Peng Yu; Hao Yang; Yi Xing; Wei-Ping Zhang; Hans Lambers; Long Li (Plant and Soil, 2022)

RIG-I acts as a tumor suppressor in melanoma via regulating the activation of the MKK/p38MAPK signaling pathway - Rui Guo; Shun-Yuan Lu; Jin-Xia Ma; Qian-Lan Wang; Lu Zhang; Ling-Yun Tang; Yan Shen; Chun-Ling Shen; Jin-Jin Wang; Li-Ming Lu; Zhu-Gang Wang; Hong-Xin Zhang (Human Cell, 2022)
Studies have indicated that RIG-I may act as a tumor suppressor and participate in the tumorigenesis of some malignant diseases. However, RIG-I induces distinct cellular responses via different downstream signaling pathways depending on the cell type. To investigate the biological function and underlying molecular mechanism of RIG-I in the tumorigenesis of melanoma, we constructed RIG-I knockout, RIG-I -overexpressing B16-F10 and RIG-I knockdown A375 melanoma cell lines, and analyzed the RIG-I-mediated change in the biological behavior of tumor cells in spontaneous and poly (I:C)-induced RIG-I activation. Cell proliferation, cell cycling, apoptosis and migration were detected by CCK-8 assay, BrdU incorporation assay, Annexin V–PI staining assay and Transwell assay, respectively. In vivo tumorigenicity was evaluated by tumor xenograft growth in nude mice and subsequently by Ki67 staining and TUNEL assays. Furthermore, Western blotting was utilized to explore the underlying mechanism of RIG-I in melanoma cells. Our data showed that RIG-I promotes apoptosis and inhibits proliferation by G1 phase cell cycle arrest in the melanoma cell lines. Mechanistically, RIG-I induced the phosphorylation of p38 MAPK and MAPK kinases MKK3 and MKK4. In conclusion, the current study demonstrated that RIG-I suppressed the development of melanoma by regulating the activity of the MKK/p38 MAPK signaling pathway, which is relevant to research on novel therapeutic targets for this malignant disease.

Acetylsalicylic acid (ASA) suppressed Fusarium rot development and neosolaniol (NEO) accumulation by activating phenylpropane metabolism in muskmelon fruit - Lan Li; Qili Liu; Huali Xue; Yang Bi; Hussain Raza; Rui Zhang; Jimdjio Kouasseu Carelle; Hui Peng; Haitao Long; Dov Prusky (European Journal of Plant Pathology, 2022)

Autism spectrum disorder-like behavior induced in rat offspring by perinatal exposure to di-(2-ethylhexyl) phthalate - Yao Li; Yun Zhao; Yu Lu; Xianxian Lu; Yingdan Hu; Qiulin Li; Menglei Shuai; Rui Li (Environmental Science and Pollution Research, 2022)

Microbial composition and nitrogen removal pathways in a novel sequencing batch reactor integrated with semi-fixed biofilm carrier: evidence from a pilot study for low- and high-strength sewage treatment - Peng-fei Chen; Rui-jian Zhang; Zhi-li Du; Guang-hua Wang; Hao-tao Dong; Bin Cui; Ru-pei Fan; Lu-xin Li; Qian-bin Wang; Ying-shi Liu; Zhi-min Sun (Environmental Science and Pollution Research, 2022)

Geographic information system and system dynamics combination technique for municipal solid waste treatment station site selection - Chen Wang; Fengqiu Zou; Jeffrey Boon Hui Yap; Rui Tang; Heng Li (Environmental Monitoring and Assessment, 2022)

Characteristics and changes of the Himalayas glacial area in China during 1990–2015 - Shu-xian Shi; Li Xing; Yue-kai Ding; Jun Dong; Rui Liu; Qin Ji; Zuo-lin Xiao; Xun Huang (Journal of Mountain Science, 2022)

Erratum to: Tracing environmental lead sources on the Ao mountain of China using lead isotopic composition and biomonitoring - Zhong-xiang Xiang; Hai-jian Bing; Yan-hong Wu; Jun Zhou; Rui Li; Xiao-li He (Journal of Mountain Science, 2022)

The functional evolution and system equilibrium of urban and rural territories - Jie Fan; Sisi Li; Zhongrui Sun; Rui Guo; Kan Zhou; Dong Chen; Jianxiong Wu (Journal of Geographical Sciences, 2022)

A study on the infection status and transmission of avian leukosis virus subgroup J in Hy-line brown roosters - Fanfeng Meng; Qiuchen Li; Rui Han; Guanlong Xu; Xintao Gao; Fubing Luo; Guangnian Shen; Xiaodong Liu; Zhifang Zhang; Peng Zhao; Guozhong Zhang (Archives of Virology, 2022)

Pelagic cyanobacterial nitrogen fixation in lakes and ponds of different latitudinal zones - Yan Li; Ye-Xin Yu; Shuo-Nan Ma; Rui-Ting Qiao; Yong-De Cui; Hai-Jun Wang; Hong-Zhu Wang (Aquatic Sciences, 2022)

Impacts of Topographic Complexity on Modeling Moisture Transport and Precipitation over the Tibetan Plateau in Summer - Gudongze Li; Haoming Chen; Mingyue Xu; Chun Zhao; Lei Zhong; Rui Li; Yunfei Fu; Yanhong Gao (Advances in Atmospheric Sciences, 2022)
The non-hydrostatic global variable resolution model (MPAS-atmosphere) is used to conduct the simulations for the South Asian Summer monsoon season (June, July, and August) in 2015 with a refinement over the Tibetan Plateau (TP) at the convection-permitting scale (4 km). Two experiments with different topographical datasets, complex (4-km) and smooth (60-km) topography, are designed to investigate the impacts of topographical complexity on moisture transport and precipitation. Compared with the observations and reanalysis data, the simulation can successfully capture the general features of key meteorological fields over the TP despite slightly underestimating the inflow through the southern TP. The results indicate that the complex topography can decrease the inward and outward moisture transport, ultimately increasing the total net moisture transport into the TP by ∼11%. The impacts of complex topography on precipitation are negligible over the TP, but the spatial distributions of precipitation over the Himalayas are significantly modulated. With the inclusion of complex topography, the sharper southern slopes of the Himalayas shift the lifted airflow and hence precipitation northward compared to the smooth topography. In addition, more small-scale valleys are resolved by the inclusion of complex topography, which serve as channels for moisture transport across the Himalayas, further favoring a northward shift of precipitation. Overall, the difference between the two experiments with different topography datasets is mainly attributed to their differing representation of the degree of the southern slopes of the Himalayas and the extent to which the valleys are resolved.

Development and perspectives of rapid detection technology in food and environment - Xue-Xia Jia; Shuang Li; Dian-Peng Han; Rui-peng Chen; Zi-Yi Yao; Bao-an Ning; Zhi-Xian Gao; Zhen-Chuan Fan (Critical Reviews in Food Science and Nutrition, 2022)

Molecular Characterization and Expression Analysis of Glutaredoxin 5 in Black Tiger Shrimp (Penaeus monodon) and Correlation Analysis Between the SNPs of PmGrx5 and Ammonia-N Stress Tolerance Trait - Rui Fan; Shigui Jiang; Yundong Li; Qibin Yang; Song Jiang; Jianhua Huang; Lishi Yang; Xu Chen; Falin Zhou (Frontiers in Marine Science, 2022)
Glutaredoxins (Grxs) are glutathione-dependent oxidoreductases that belong to the thioredoxin (Trx) superfamily and are an essential part of the redox system in living organisms. However, there is a serious lack of sequence information and functional validation associated with Grxs in crustaceans. In this study, a new Grx gene ( PmGrx5 ) was identified and characterized in black tiger shrimp ( Penaeus monodon ). The full-length cDNA of PmGrx5 is 787 bp and consists of 114 bp 5′-UTR, 232 bp 3′-UTR, and 441 bp ORF, encoding a hypothetical protein of 146 amino acids. The putative PmGrx5 protein is 16.27 kDa with a theoretical isoelectric point of 5.90. Sequence alignment showed that PmGrx5 had the highest amino acid sequence homology with Grx5 from Penaeus vannamei at 98.63% and clustered with Grx5 from other crustaceans. Quantitative real-time PCR (qRT-PCR) analysis showed that PmGrx5 was expressed in all tissues examined, with a higher expression in the testis, stomach, lymphoid organ, and gill. PmGrx5 was continuously expressed during development, with the highest expression in zoea I. Ammonia-N stress and bacterial infection both differentially upregulated PmGrx5 expression in the hepatopancreas and gill. In addition, when PmGrx5 was inhibited, the expression of some other antioxidant enzymes was upregulated at the beginning of ammonia-N stress, but as the stress time increased, the expression of antioxidant enzymes was inhibited, the expression of apoptotic genes was increased, and the GSH content was significantly reduced. Inhibition of PmGrx5 led to a greater risk of oxidative damage in shrimp. In addition, the relationship between SNPs in exons of the PmGrx5 gene and tolerance to ammonia-N stress was identified and analysed. A total of nine SNPs were successfully identified, eight of which were significantly associated with ammonia and nitrogen stress tolerance trait in shrimp ( P < 0.05). The present study shows that PmGrx5 is involved in redox regulation and plays an important role in shrimp resistance to marine environmental stresses. Meanwhile, this study will provide a basis for molecular marker breeding in shrimp.

Phosphorus Absorption and Excretion in Hybrid Sturgeon (Huso dauricus♀ X Acipenser schrenckii♂) Intubated with Different Ca/P Ratios - Jiali Jin; Zhipeng Chu; Rui Ruan; Wei Liu; Xihua Chen; Chuangju Li (Fishes, 2022)
To study the effect of Ca/P ratio on the P and Ca absorption and excretion in hybrid sturgeon (Huso dauricus♀ X Acipenser schrenckii♂), five groups of fish were intubated with 100 mg P·kg−1 BW with the Ca/P ratios of 0:1, 0.25:1, 0.5:1, 1:1, and 2:1. Plasma P concentrations were significantly elevated at Ca/P ratios below 2:1, and the highest value was obtained at Ca/P ratio of 0.5:1. Plasma Ca content was significantly increased at the highest Ca/P ratio. Urine P excretion rate in the fish intubated with Ca/P ratio of 0.5:1 was significantly higher than that of the groups with Ca/P ratios of 0:1 and 2:1. The highest urea excretion rates were observed at Ca/P ratio of 0.5:1 and 1:1. The total P excretion at 48 h post intubation reached about 30 mg·kg−1 BW, which was recorded for the group with Ca/P ratio of 0.5:1. The present study showed that P absorption efficiency was improved in hybrid sturgeon at Ca/P ratio of 0.5:1, indicating that P inclusion level in sturgeon feed can be further optimized to reduce dietary P input and lower the excessive undigested P discharge into the rearing water.

Otolith Marking With Strontium for Stock Assessment in Coilia nasus - Ming-Zhi Liu; Ri-jin Jiang; Hui Zhang; Fan Yang; Xia-Fang Li; Guang-Peng Feng; Rui Yin; Feng Chen (Frontiers in Marine Science, 2022)
Mass stock enhancement and release are excellent ways to recover Coilia nasus resources. However, it is challenging to evaluate stock enhancement effectively, and it is important to establish a method suitable for estimating C. nasus populations. We explored the effectiveness of marking otoliths in these fish with strontium by immersing C. nasus in hexahydrate strontium chloride solutions. We used laser ablation inductively coupled plasma mass spectrometry to measure the strontium content of otoliths and fish bodies. The larvae (40 d post hatch) were reared in five different concentrations of strontium (0, 12, 24, 48, and 60 mg/L) for 7 d, followed by treatment in non-additive water for 3 wk. The results showed that the cumulative mortality rate was not significantly different between treatment and control groups ( P >0.05), except in the group treated with 24 mg/L strontium. The swimming and feeding behaviors did not change significantly, indicating that strontium did not negatively affect survival in this species. The strontium/calcium ratios of otoliths in the control group were stable (1.78–2.32 mmol/mol), whereas those of the experimental (marked) groups ranged widely (4.47–61.02 mmol/mol). The strontium/calcium ratios increased with increasing strontium concentration, but gradually returned to baseline values, resulting in a 100% success rate of marking with strontium. Following immersion in 12 mg/L strontium, strontium levels in the body returned to normal after 24 d. In summary, a treatment of 12 mg/L strontium for 4 d was identified as viable for marking. We confirmed the feasibility of strontium marking for the mass marking and release of C. nasus . This marking method does not affect the physiology of the fish and may provide a new approach for reasonable and scientific stock assessment of C. nasus post hatch.

Risk Evaluation of Navigation Environment Based on Dynamic Weight Model and Its Application - Shuzhe Chen; Lei Wu; Cheng Xie; Li Zhou; Rui Wang; Zhao Liu; Quanlong Zhu; Lianzhong Zhu (Journal of Marine Science and Engineering, 2022)
In order to scientifically and reasonably evaluate the safety risk of ship navigation, to and better solve the problems of the poor sensitivity of static evaluation and insufficient ability to grasp the overall dynamic situation, in this paper, representative safety evaluation indexes for ship navigation are screened and the initial weight of each index is confirmed in combination with the improved analytic hierarchy process (IAHP), in order to learn the changes of navigation environment and accident samples in the waters in the jurisdiction. Finally, the dynamic risk evaluation is carried out by constructing a dynamic weight evaluation model for the safety risk of the navigation environment based on the weight fusion of subjective and objective impact factors. The waters under the jurisdiction of Sanya, China were selected for the study, and the navigation risk of the waters in the jurisdiction was calculated by using the dynamic weight evaluation model based on navigation risk. The calculation results are highly consistent with the results based on the statistics of historical accidents and the analysis of the characteristics of the navigation environment in the jurisdiction. The navigation risk in this water area is the greatest from May to September every year. The dynamic weight evaluation model can not only overcome the subjective evaluation distortion in the traditional risk evaluation theory of navigation environment in practical applications, but can also provide a scientific theoretical basis for the dynamic evaluation and early warning of the risk of ship navigation environments through continuous sample learning.

Bone Marrow-Derived Alk1 Mutant Endothelial Cells and Clonally Expanded Somatic Alk1 Mutant Endothelial Cells Contribute to the Development of Brain Arteriovenous Malformations in Mice - Sonali S. Shaligram; Rui Zhang; Wan Zhu; Li Ma; Man Luo; Qiang Li; Miriam Weiss; Thomas Arnold; Nicolas Santander; Rich Liang; Leandro do Prado; Chaoliang Tang; et al. (Translational Stroke Research, 2022)

Clinical Reference Strategy for the Selection of Treatment Materials for Maxillofacial Bone Transplantation: A Systematic Review and Network Meta-Analysis - Shuxin Zhang; Xinyi Zhang; Yanli Li; Xuran Mao; Rui Liu; Yanxin Qi; Eui-Seok Lee; Heng Bo Jiang (Tissue Engineering and Regenerative Medicine, 2022)

Sandstorms cause shrinkage of Haloxylon ammodendron shrubs and limit their self-renewal - Sheng-bo Shi; Dang-wei Zhou; Fang-lin Wang; Rui Shi; Tao Sun; Tian-cai Li; Jia-lin Ma; Xiang Wan; Jian-ping Ma; Jing-nian Tang (Theoretical and Experimental Plant Physiology, 2022)
Haloxylon ammodendron is an excellent windproof and sand-fixing species whose shrubs are widely cultivated in arid desert areas of northwest China but are now at risk of degradation and shrinkage. Using the chlorophyll fluorescence image analysis technique, the response of photosystem II (PSII) photochemical efficiency and non-photochemical quenching capacity to sediment-carrying wind and sand-free wind (both 12 m s −1 ) lasting for 10, 20, and 40 min were studied with seedlings in a wind tunnel. The results indicated that the sand-free wind had little influence on the maximum quantum efficiency of PSII photochemistry, F v / F m , which was approximately 0.80 on average; however, the F v / F m decreased over exposure time in the sediment-carrying wind group, with values smaller than those in the wind-only group. The non-photochemical quenching was sensitive to wind erosion, and sediment-carrying wind could aggravate the reduction in non-photochemical quenching ( NPQ ). Except for the 10 min duration, the maximum quantum efficiency of PSII photochemistry after dark recovery for 15 min, F v r / F m r , was lower in seedlings exposed to sediment-carrying wind than in those in the wind-only group. Compared to wind-only, wind-blown sand led to a water imbalance and withering in seedlings, causing the concentration of photosynthetic pigments (when based on the fresh mass of green branches) to not decrease. With a longer exposure time to sediment-carrying wind, both the probability and extent of lignified spots occurring increased in green assimilative branches. Our results demonstrated that sediment-carrying wind at 12 m s −1 lasting for 20 min or more could cause irreversible damage to the photosynthetic apparatus of H. ammodendron seedlings. Therefore, frequent and strong sandstorms are the main disturbance factors leading to shrinkage of shrubs and limiting their self-renewal.

Erratum to: Generating broad-spectrum tolerance to ALS-inhibiting herbicides in rice by base editing - Rui Zhang; Sha Chen; Xiangbing Meng; Zhuangzhuang Chai; Delin Wang; Yuge Yuan; Kunling Chen; Linjian Jiang; Jiayang Li; Caixia Gao (Science China Life Sciences, 2022)

Genetically encoded redox biosensor system for H2O2 measurement in four subcellular compartments in acute myeloid leukemia (AML) cells - Mengmeng Cui; Ghulam Abbas; Dianbing Wang; Qian Liu; Rui Gong; Min Li; Xian-En Zhang (Science China Life Sciences, 2022)

Diagnostic Performance of miR-485-3p in Patients with Parkinson’s Disease and its Relationship with Neuroinflammation - Xia Lin; Rui Wang; Ran Li; Taotao Tao; Danhong Zhang; Yuxiang Qi (NeuroMolecular Medicine, 2022)

Extracellular vesicles derived from human Sertoli cells: characterizations, proteomic analysis, and miRNA profiling - Xiao-Hui Tan; Sheng-Ji Gu; Wen-Jie Tian; Wen-Peng Song; Yang-Yang Gu; Yi-Ming Yuan; Xue-Song Li; Zhong-Cheng Xin; Sae Woong Kim; Rui-Li Guan; Woong Jin Bae (Molecular Biology Reports, 2022)

The interplay of particle properties and solution chemistry on aggregation kinetics of soil nanoparticles - Ning Hu; Chen-yang Xu; Zeng-chao Geng; Fei-nan Hu; Qi-rui Li; Ren-tian Ma; Qiang Wang (Journal of Soils and Sediments, 2022)

Effects of Biochar on the Growth, Ginsenoside Content, and Soil Microbial Community Composition of Panax quinquefolium L - Xiaotong Yang; Zhifang Ran; Rui Li; Lei Fang; Jie Zhou; Lanping Guo (Journal of Soil Science and Plant Nutrition, 2022)

Holocene-Anthropocene transition in northwestern Yunnan revealed by records of soil erosion and trace metal pollution from the sediments of Lake Jian, southwestern China - Rui Yang; Duo Wu; Zehui Li; Zijie Yuan; Lili Niu; Huan Zhang; Jie Chen; Aifeng Zhou (Journal of Paleolimnology, 2022)

Establishment and optimization of PEG-mediated protoplast transformation in the microalga Haematococcus pluvialis - Chunli Guo; Muhammad Anwar; Rui Mei; Xinyi Li; Di Zhao; Yanan Jiang; Jieyi Zhuang; Chen Liu; Chaogang Wang; Zhangli Hu (Journal of Applied Phycology, 2022)
Genetic manipulation of Haematococcus pluvialis is difficult because of the lack of a stable and convenient transformation system. The pH124-EGFP-Ble vector containing ble as a selective gene and EGFP as a reporter gene was constructed and employed for effective transformation. H. pluvialis protoplasts were obtained by treating with cellulase and macerozeme. Then polyethylene glycol-mediated transformation was established by incubating the protoplast with the vector. To improve the transformation efficiency of H. pluvialis protoplasts, the transformation system was optimized in consideration of different influencing factors, including zeomycin concentration, growth stage, amount of transformed vector, linearization of the vector, and duration of low-intensity illumination. The integration and expression of ble and EGFP was confirmed in the transformants. Moreover, the optimal combination for protoplast transformation of H. pluvialis was determined to be 5 µg of the linearized vector used to transform cells in the log growth phase, and then the transformed protoplasts allowed to recover under low-intensity illumination for 6 h. This study represents and describes the successful development of an H. pluvialis transformation protocol using protoplasts, which will enable convenient genetic manipulation of this important algal species.

C2CD4A/B variants in the predisposition of lung cancer in the Chinese Han population - Feifei Han; Lu Qian; Yi Zhang; Ping Liu; Rui Li; Mingwei Chen (Functional & Integrative Genomics, 2022)

Occurrence, Controlling Factors and Health Risks of Cr6+ in Groundwater in the Guanzhong Basin of China - Lei Wang; Peiyue Li; Rui Duan; Xiaodong He (Exposure and Health, 2022)

Response of bacterial communities in saline-alkali soil to different pesticide stresses - Juan Che; Yan Lei Zhu; Yan Hong Li; Rui Zhang; Zhi Yong Ruan; Wei Zhang (Environmental Science and Pollution Research, 2022)

Assessing residual motor function in patients with disorders of consciousness by brain network properties of task-state EEG - Lipeng Zhang; Rui Zhang; Yongkun Guo; Dexiao Zhao; Shizheng Li; Mingming Chen; Li Shi; Dezhong Yao; Jinfeng Gao; Xinjun Wang; Yuxia Hu (Cognitive Neurodynamics, 2022)

Aberrant Gene Expression of Selenoproteins in Chicken Spleen Lymphocytes Induced by Mercuric Chloride - Jia-Hong Chu; Yu-Xue Yan; Xue-Wei Chen; Pei-Chao Gao; Lan-Xin Li; Rui-Feng Fan (Biological Trace Element Research, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Failure mechanisms and risk mitigation of check dams on the Chinese Loess Plateau: A case study at the Gutun Gully - Rui-jun Jiang; Mao-sheng Zhang; Li Feng; Ping-ping Sun (Journal of Mountain Science, 2022)

China’s food security situation and key questions in the new era: A perspective of farmland protection - Xinyuan Liang; Xiaobin Jin; Bo Han; Rui Sun; Weiyi Xu; Hanbing Li; Jie He; Jin Li (Journal of Geographical Sciences, 2022)

Combining double probability distribution functions to unmix bimodal grain-size distributions of sediments - Rui Xu; Rui Yuan; Donghui Li; Liang Xu; Mingfeng Gu (Arabian Journal of Geosciences, 2022)

Logging evaluation of shale oil “sweet spot” in Da’anzhai member, Longgang area, Sichuan Basin - Zonghui Lin; Jungang Lu; Rui Zhang; Shaoming Zhang; Longxiang Tang; Zhanghao Liu; Yaoting Li (Arabian Journal of Geosciences, 2022)

Effects of dietary protein concentration on growth and anti-oxidant capacity of coho salmon Oncorhynchus kisutch (Walbaum, 1792) alevins - Cong-mei Xu; Hai-rui Yu; Qin Zhang; Ling-yao Li; Jing-jing Fan; Meng-jie Guo; Fang-hui Li; Xiang-yi Qiu; Ling-ling Shan (Aquaculture International, 2022)

In vitro Scolicidal Efficacy of 5-Fluorouracil and Radiation Against Protoscoleces of Echinococcus granulosus Sensu Lato - Pengfei Lu; Jun Li; Rui Mao; Hongzhi Qi; Liping Yang; Qin Zhou; Mengxiao Tian; Wenbao Zhang; Yongxing Bao (Acta Parasitologica, 2022)

Toxic encephalopathy induced by radix Sophorae tonkinensis - Xue-Lin Li; Hao-Tian Zhao; Jinming Han; Zhong-Rui Yan; Hai-Yang Wang (Acta Neurologica Belgica, 2022)

Laboratory and centrifugal model tests on failure mechanism of canal slopes under cyclic action of wetting–drying - Rui Zhu; Ying-hao Huang; Chen Zhang; Wan-li Guo; Hao Chen (European Journal of Environmental and Civil Engineering, 2022)

Metagenomic analysis reveals wide distribution of phototrophic bacteria in hydrothermal vents on the ultraslow-spreading Southwest Indian Ridge - Hong Chen; Deng Hui Li; Ai Jun Jiang; Xue Gong Li; Shi Jun Wu; Jian Wei Chen; Meng Jie Qu; Xiao Qing Qi; Jie Dai; Rui Zhao; Wei-Jia Zhang; Shan Shan Liu; et al. (Marine Life Science & Technology, 2022)

The level of endogenous JA is critical for activation of SA- and JA-defensive signaling pathway in japonica rice cultivar Ziyu44 upon Magnaporthe oryzae infection - Xingyu An; Hui Zhang; Jinlu Li; Rui Yang; Qianchun Zeng; Mo Wang; Qiong Luo (Journal of Plant Pathology, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Hippocampal Activated Microglia May Contribute to Blood–Brain Barrier Impairment and Cognitive Dysfunction in Post-Traumatic Stress Disorder-Like Rats - Kun Ni; Jixiang Zhu; Xuan Xu; Yue Liu; Shuai Yang; Yulin Huang; Rui Xu; Li Jiang; Juan Zhang; Wei Zhang; Zhengliang Ma (Journal of Molecular Neuroscience, 2022)

Long noncoding RNA MIR3142HG accelerates lipopolysaccharide-induced acute lung injury via miR-95-5p/JAK2 axis - Yanqiu Gao; Shuangfeng Li; Rui Dong; Xiaoyan Li (Human Cell, 2022)

Association between glucagon-like peptide-1 receptor gene polymorphism and treatment response to GLP1R agonists in Chinese patients with type 2 diabetes: a prospective cohort study - Ziwan Guan; Yue Du; Rui Li; Shufang Zhang; Yuedong Xu; Xiaoqian Zhang; Fan Zhang; Ying Yin; Kunrong Wu; Xiaoli Li; Yan Li (European Journal of Clinical Pharmacology, 2022)

Spatiotemporal evolution of chlorophyll-a concentration from MODIS data inversion in the middle and lower reaches of the Hanjiang River, China - Zhuo Chen; Ming Dou; Rui Xia; Guiqiu Li; Lisha Shen (Environmental Science and Pollution Research, 2022)

Antibiotic resistomes in water supply reservoirs sediments of central China: main biotic drivers and distribution pattern - Kai Zhang; Kuangjia Li; Rui Xin; Ya Han; Ziwei Guo; Wei Zou; Wei Wei; Xiangchao Cui; Zhongshuai Zhang; Ying Zhang (Environmental Science and Pollution Research, 2022)

Cardiac Expression of Esophageal Cancer-Related Gene-4 is Regulated by Sp1 and is a Potential Early Target of Doxorubicin-Induced Cardiotoxicity - Dandan Long; Chunyue Chen; Wei Li; Wanling Peng; Dongmei Li; Rui Zhou; Xitong Dang (Cardiovascular Toxicology, 2022)

Geochronological, geochemical, and P–T path constraints on the late Paleoproterozoic continent–continent collision orogeny in the Quruqtagh Block, Tarim Craton - Tao Cui; Shan-Shan Li; Rui-Qing Guo; Germain Bishikwabo; Xiang-Kuan Gong; Gui-Ping Liu; Yu Guo (Arabian Journal of Geosciences, 2022)

A novel microRNA regulates cooperation between symbiont and a laterally acquired gene in the regulation of pantothenate biosynthesis within Bemisia tabaci whiteflies - Xiang Sun; Bing‐Qi Liu; Chu‐Qiao Li; Zhan‐Bo Chen; Xiao‐Rui Xu; Jun‐Bo Luan (Molecular Ecology, 2022)
Horizontally transferred genes (HTGs) play a key role in animal symbiosis, and some horizontally transferred genes or proteins are highly expressed in specialized host cells (bacteriocytes). However, it is not clear how HTGs are regulated, but microRNAs (miRNAs) are prime candidates given their previously demonstrated roles in symbiosis and impacts on the expression of host genes. A horizontally acquired PanBC that is highly expressed in whitefly bacteriocytes can cooperate with an obligate symbiont Portiera for pantothenate production, facilitating whitefly performance and Portiera titre. Here, we found that a whitefly miRNA, novel‐m0780‐5p, was up‐regulated and its target panBC was down‐regulated in Portiera ‐eliminated whiteflies. This miRNA was located in the cytoplasmic region of whitefly bacteriocytes. Injection of novel‐m0780‐5p agomir reduced the expression of PanBC in whitefly bacteriocytes, while injection of novel‐m0780‐5p antagomir enhanced PanBC expression. Agomir injection also reduced the pantothenate level, Portiera titre and whitefly performance. Supplementation with pantothenate restored Portiera titre and the fitness of agomir‐injected whiteflies. Thus, we demonstrate that a whitefly miRNA regulates panBC ‐mediated host–symbiont collaboration required for pantothenate synthesis, benefiting the whitefly– Portiera symbiosis. Both panBC and novel‐m0780‐5p are present in the genomes of six Bemisia tabaci species. The expression of a novel miRNA in multiple B . tabaci species suggests that the miRNA evolved after panBC acquisition, and allowed this gene to be more tightly regulated. Our discovery provides the first account of a HTG being regulated by a miRNA from the host genome, and suggests key roles for interactions between miRNAs and HTGs in the functioning of symbiosis.

Numerical Study on the Influence of Tropical Cyclone Characteristics on the Sea State and Sea Surface Roughness inside the Tropical Cyclones - Shuiqing Li; Rui Li; Yanjun Wang; Jiuyou Lu (Journal of Marine Science and Engineering, 2022)
The development of wind wave (i.e., sea state) inside an intense tropical cyclone (TC) is the dominant contributor to the sea surface roughness and thus significantly impacts the air–sea interaction. The sea state is known to vary with TC characteristics (intensity, size, and translation speed); however, comprehensive knowledge of the influence of TC characteristics on the sea state and sea surface roughness is quite limited, largely because of the lack of observations. In this study, numerical experiments are performed to investigate the influence of TC characteristics on the sea state and the sea surface roughness under a range of idealized TCs. The numerical results indicate that the sea states are systematically younger for a more intense or smaller TC, and their azimuthal variation is predominantly determined by the TC translation. The dependence of the sea surface roughness on wind speed shows systematic variations with the TC characteristics, which are most significant for a moderately moving TC.

Cultivation and Functional Characterization of a Deep-Sea Lentisphaerae Representative Reveals Its Unique Physiology and Ecology - Tianhang Zhang; Rikuan Zheng; Rui Liu; Ronggui Li; Chaomin Sun (Frontiers in Marine Science, 2022)
As a member of Planctomycetes – Verrucomicrobia – Chlamydia (PVC) superphylum, the phylum Lentisphaerae is broadly distributed in various environments. Lentisphaerae members have been recognized as being typically difficult to isolate in pure culture—only five strains belonging to this phylum were cultured up to now—and therefore their major physiology and ecology are largely unknown. Here, using a polysaccharide degradation-driven strategy, we successfully cultured a representative of Lentisphaerae bacteria ( Candidatus Coldseepensis marina zth2) from the deep-sea cold seep. Based on physiological and phylogenetic analyses, strain zth2 is identified as a type strain of a novel family. Notably, strain zth2 divides by a budding manner and a unique feature seen in ultrathin-section electron microscopic observation is the occurrence of narrow protrusions, namely, both cell wall and cytoplasm on the surface of strain zth2. Through growth assays and transcriptomic analyses, strain zth2 was verified to efficiently utilize polysaccharides, phosphate, and iron for growth. Strikingly, the utilization of polysaccharide, phosphate, and iron is correlative and jointly contributes to carbon, phosphorus, and iron metabolisms and thereby facilitating the production of energy. By mimicking the ocean environment and using operational taxonomic units (OTUs) analysis, we demonstrated that strain zth2 significantly enrich the microbial diversity by metabolizing polysaccharides or other substances. Overall, we propose that Lentisphaerae members are potential contributors to the cycling of nutrient, carbon, phosphorus, and other elements in the deep biosphere.

Research progress on antimicrobial materials for food packaging - Saeed Ahmed; Dur E. Sameen; Rui Lu; Rui Li; Jianwu Dai; Wen Qin; Yaowen Liu (Critical Reviews in Food Science and Nutrition, 2022)

Two new dammarane-type triterpenoids from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hui-Rui Gao; Hong-Juan Song; Dan-Da Ma; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Xiao-Li Wang; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Flavonoid glycosides from the nectar of Camellia reticulata Lindl. - Xin-Lan Chen; Xing-Rong Peng; Xue-Yang Gong; Yi-Qiu Liu; Zhuo Qing; Xiao-Xiao Ren; Rui Su; Li-Ming Fang; Ming-Hua Qiu; Kun Dong (Natural Product Research, 2022)

Chrysomutanin and related meroterpenoids from a DES mutant of the marine-derived fungus Penicillium chrysogenum S-3-25 - Hua Qiao; Shu-Hua Zhang; Yuan Dong; Yu Yang; Rui Xu; Bo Chen; Yi Wang; Tian-Jiao Zhu; Cheng-Bin Cui; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2022)

A point cloud registration method based on dual quaternion description with point-linear feature constraints - Raobo Li; Xiping Yuan; Shu Gan; Rui Bi; Yan Guo; Sha Gao (International Journal of Remote Sensing, 2022)

Effects of different energy diets on DNA methylation and mRNA expression in follicle stimulating hormone receptor gene promoter region of Duolang sheep during estrus - Bo Liu; Hongjian Li; Weikun Tao; Fei Huang; Xue Rui; Jie Wang; Peng Niu; Di Fang; Qinghua Gao (Molecular Biology Reports, 2022)

Physiological homeostasis alteration and cellular structure damage of Chlorella vulgaris exposed to silver nanoparticles with various microstructural morphologies - Ningcan Deng; Haibo Li; Yinghua Li; Fan Mo; Mingshuai Wang; Zhe Li; Xi Chen; Jianing Xu; Rui Chai; Hongxuan Wang (Environmental Science and Pollution Research, 2022)

Structure identification of a karst groundwater system based on high-resolution rainfall-hydrological response characteristics - Zongxing Wang; Rui Wu; Kun Huang; Yang Qiu; Zhongxia Li; You Lv; Junwei Wan (Environmental Science and Pollution Research, 2022)

Interaction between organic matter and tetracycline in river sediments in cold regions - Changyong Wu; Rui Tang; Huiqi Li; Xiang Liu; Liya Fu; Yin Yu; Chunli Wan (Environmental Science and Pollution Research, 2022)

AT1 Receptors: Their Actions from Hypertension to Cognitive Impairment - Hanxue Wu; Qi Sun; Shenglan Yuan; Jiawei Wang; Fanni Li; Hongli Gao; Xingjuan Chen; Rui Yang; Jiaxi Xu (Cardiovascular Toxicology, 2022)

Focal white matter microstructural alteration after anthracycline-based systemic treatment in long-term breast cancer survivors: a structural magnetic resonance imaging study - Huawen Zhang; Peng Li; Tonghui Liu; Xueyuan Wang; Wei Feng; Rui Chen; Hengyang Wei; Guoqiang Li; Long Ning; Ming Zhang; Yuchen Zhang (Brain Imaging and Behavior, 2022)

Development of a Label-Free Colorimetric Aptasensor with Rationally Utilized Aptamer for Rapid Detection of Okadaic Acid - Xiaochen Yan; Xiaoyan Qi; Yinglin Zhao; Ling Li; Rui Ma; Lele Wang; Sai Wang; Xiangzhao Mao (Journal of Ocean University of China, 2022)

Experimental study on the mechanical properties and energy evolution of hard rock during water immersion - Fan-Bo Wei; Bing-Rui Chen; Rui Wang; Guo-Liang Li; Tao Li; Xu Wang; Xin-Hao Zhu (Arabian Journal of Geosciences, 2022)

Multiple fracture, dissolution, and cementation events of Ordovician carbonate reservoirs in T-SH Oilfield, Tarim Basin - Teng Zhao; Rui Zhao; Chongyang Xiao; Jun Han; Anpeng Kuang; Yingtao Li (Arabian Journal of Geosciences, 2022)

Decadal shift of the influence of Arctic Oscillation on dust weather frequency in spring over the Middle East during 1974–2019 - Yijie Sun; Rui Mao; Dao‐Yi Gong; Ying Li; Seong‐Joong Kim; Xiao‐Xiao Zhang; Xuezhen Zhang; Mehdi Hamidi (International Journal of Climatology, 2022)
Dust weather has an impact on human health and climate change in the Middle East. In this study, we examined the influence of the Arctic Oscillation (AO) on spring dust weather frequency over the Middle East at an interannual timescale during 1974–2019. The results show that there was an interdecadal shift of the influence of AO on dust weather frequency in the Middle East, with a correlation coefficient between the AO index and dust weather frequency changing from −0.52 during 1974–1994 period (P1) to 0.49 during 1995–2013 period (P2). During P1, negative correlations between AO index and dust weather frequency were found over the northern Arabian Peninsula, and during P2, positive ones were mostly over the central and southwestern Arabian Peninsula. In the lower and middle troposphere, negative geopotential height anomalies are associated with the negative phase of the AO over South Europe during P1, whereas negative geopotential height anomalies are associated with the positive phase of the AO over Northeast Africa during P2. The negative height anomalies resulted in the occurrence of more low‐pressure systems and, thus, dust weather in the Middle East. It is found that the interdecadal shift of the influence of the AO on dust weather was related to an AO‐related northward displacement of wave train propagation during P2. Specifically, during P1 period, the northern branch of AO‐related wave train dominated over the middle latitudes of the North Atlantic across South Europe to the Arabian Peninsula, which resulted in the negative height anomaly over South Europe in the lower and middle troposphere. However, during P2 period, the AO‐related wave train propagation moved northward, and then, the southern branch of the AO‐related wave train dominated over the low latitudes of the North Atlantic across northern Africa to the Arabian Peninsula, which played an important role in the formation of the negative height anomalies over Northeast Africa.

Alkaloids constituents from the roots of Phragmites australis (Cav.) Trin. ex Steud. with their cytotoxic activities - Ying Chen; Li Li; Li-Rui Jiang; Jia-Yin Tan; Li-Na Guo; Xiao-Li Wang; Wei Dong; Wen-Bao Wang; Ji-Kai Sun; Bo Song (Natural Product Research, 2022)

Petrogenesis and tectonic setting of the early-middle triassic subduction-related granite in the eastern segment of East Kunlun: evidences from petrology, geochemistry, and zircon U-Pb-Hf isotopes - Zuo-Chen Li; Xian-Zhi Pei; Paul D. Bons; Rui-Bao Li; Lei Pei; Guo-Chao Chen; You-Xin Chen; Cheng-Jun Liu; Meng Wang; Shao-Wei Zhao; Xiao-Bing Li; Feng Gao (International Geology Review, 2022)

Two new sesquiterpenes from the rhizomes of Atractylodes macrocephala and their biological activities - Yi-Nan Zhao; Gai Gao; Jin-Lian Ma; Rui-Zhu Xu; Tao Guo; Li-Min Wu; Xin-Guang Liu; Zhi-Shen Xie; Jiang-Yan Xu; Zhen-Qiang Zhang; Pan Wang (Natural Product Research, 2022)

Evaluation and optimal selection of Dunhuang radiometric calibration site based on OLI/Landsat 8 and MSI/Sentinel 2 data - Sifeng Zhu; Zhengqiang Li; Xiuqing Hu; Lili Qie; Hua Xu; Rui Qiao; Yuhuan Zhang; Philippe Golry (International Journal of Remote Sensing, 2022)

Genome-Wide Identification of WUSCHEL-Related Homeobox Gene Family and their Expression Analysis During Somatic Embryogenesis in Oil Palm (Elaeis guineensis) - Anni Zhang; Yinchun Li; Rajesh Yarra; Rui Li; Hongxing Cao; Longfei Jin (Tropical Plant Biology, 2022)

Mechanism of Adipose-Derived Mesenchymal Stem Cell-Derived Extracellular Vesicles Carrying miR-21-5p in Hyperoxia-Induced Lung Injury - Yunfei Wu; Zhihui Zhang; Jun Li; Hai Zhong; Rui Yuan; Zihui Deng; Xu Wu (Stem Cell Reviews and Reports, 2022)

A switch-on molecular biosensor for detection of caspase-3 and imaging of apoptosis of cells - Rui Gong; Dianbing Wang; Ghulam Abbas; Shimin Li; Qian Liu; Mengmeng Cui; Xian-En Zhang (Science China Life Sciences, 2022)

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Glacier lanternfish (Benthosema glaciale) first found on the continental slope of the Pacific Arctic - Ran Zhang; Yuan Li; Qiaohong Liu; Puqing Song; Hai Li; Rui Wang; Shaoxiong Ding; Longshan Lin (Polar Biology, 2022)

Identification and Expression Analysis of the SBP-box Gene Family Related to Abiotic Stress in Tea Plant (Camellia sinensis (L.) O. Kuntze) - Rui-Min Teng; Yong-Xin Wang; Hui Li; Hao Liu; Yu Wang; Jing Zhuang (Plant Molecular Biology Reporter, 2022)

QTL mapping and candidate gene prediction for fiber yield and quality traits in a high-generation cotton chromosome substitution line with Gossypium barbadense segments - Quanwei Lu; Pengtao Li; Rui Yang; Xianghui Xiao; Ziyin Li; Qiuyu Wu; Juwu Gong; Qun Ge; Aiying Liu; Shengli Du; Jundi Wang; Yuzhen Shi; et al. (Molecular Genetics and Genomics, 2022)

SSR analysis and fingerprint construction to evaluate the genetic diversity of medicinal plum varieties - Rui Wang; Xin Li; Wei Zhang; Jinmei Ou; Chengwu Fang; Qianqian Song; Huiyin Zhou (Journal of Plant Biochemistry and Biotechnology, 2022)

Sulfoxaflor resistance in Aphis gossypii: resistance mechanism, feeding behavior and life history changes - Li Wang; Li Cui; Qinqin Wang; Yanpeng Chang; Weiling Huang; Changhui Rui (Journal of Pest Science, 2022)

Neuroprotective effect of aldose reductase knockout in a mouse model of spinal cord injury involves NF-κB pathway - Fu-xin Han; Rui Zhang; Xin-xing Yang; Shan-bo Ma; Shi-jie Hu; Bing Li (Experimental Brain Research, 2022)

Identification of epigenetic modifications mediating the antagonistic effect of selenium against cadmium-induced breast carcinogenesis - Zhuo-Zhi Liang; Yi-Xin Zhang; Rui-Mei Zhu; Yue-Lin Li; Hong-Mei Jiang; Ruo-Bi Li; Qian-Xin Chen; Qing Wang; Lu-Ying Tang; Ze-Fang Ren (Environmental Science and Pollution Research, 2022)

Analysis of geomorphologic features of the circular structure in the south of Lufeng Dinosaur Valley - Hu Lin; Gan Shu; Yuan Xiping; Yang MingLong; Gao Sha; Bi Rui; Li Yan (Earth Science Informatics, 2022)

Physiological Responses of Ribosomal Protein S12 K43 Mutants of Corynebacterium glutamicum - Guihong Zhao; Rui Su; Meng Yuan; Hongkun Ma; Taidong Bo; Hao Jiang; Chen Wu; Yanjun Li (Current Microbiology, 2022)

Alleviative Effects of Exercise on Bone Remodeling in Fluorosis Mice - Rui Li; Zeen Gong; Yanghuan Yu; Ruiyan Niu; Shengtai Bian; Zilong Sun (Biological Trace Element Research, 2022)

The Antioxidant Role of Selenium via GPx1 and GPx4 in LPS-Induced Oxidative Stress in Bovine Endometrial Cells - Samson O. Adeniran; Peng Zheng; Rui Feng; Elikanah O. Adegoke; Fushuo Huang; Mingjun Ma; Ziming Wang; Olamigoke O. Ifarajimi; Xiaoyu Li; Guixue Zhang (Biological Trace Element Research, 2022)

Projected change in precipitation forms in the Chinese Tianshan Mountains based on the Back Propagation Neural Network Model - Rui Ren; Xue-mei Li; Zhen Li; Lan-hai Li; Yi-yu Huang (Journal of Mountain Science, 2022)

Anaerobic digestion characteristics and key microorganisms associated with low-temperature rapeseed cake and sheep manure fermentation - Li Liu; Rongbo Xiong; Yi Li; Laisheng Chen; Rui Han (Archives of Microbiology, 2022)

Microseismic signal denoising by combining variational mode decomposition with permutation entropy - Zhang Xing-Li; Cao Lian-Yue; Chen Yan; Jia Rui-Sheng; Lu Xin-Ming (Applied Geophysics, 2022)

Dysfunction of FadA‐cAMP signalling decreases Aspergillus flavus resistance to antimicrobial natural preservative Perillaldehyde and AFB1 biosynthesis - Kunlong Yang; Qingru Geng; Yue Luo; Rui Xie; Tongzheng Sun; Zhen Wang; Ling Qin; Wei Zhao; Man Liu; Yongxin Li; Jun Tian (Environmental Microbiology, 2022)
Summary Aspergillus flavus is an opportunistic fungal pathogen that colonizes agriculture crops with aflatoxin contamination. We found that Perillaldehyde (PAE) effectively inhibited A . flavus viability and aflatoxin production by inducing excess reactive oxygen species (ROS). Transcriptome analysis indicated that the Gα protein FadA was significantly induced by PAE. Functional characterization of FadA showed it is important for asexual development and aflatoxin biosynthesis by regulation of cAMP‐PKA signalling. The Δ fadA mutant was more sensitive to PAE, while Δ pdeL and Δ pdeH mutants can tolerate excess PAE compared to wild‐type A . flavus . Further RNA‐sequence analysis showed that fadA was important for expression of genes involved in oxidation–reduction and cellular metabolism. The flow cytometry and fluorescence microscopy demonstrated that Δ fadA accumulated more concentration of ROS in cells, and the transcriptome data indicated that genes involved in ROS scavenging were downregulated in Δ fadA mutant. We further found that FadA participated in regulating response to extracellular environmental stresses by increasing phosphorylation levels of MAPK Kinase Slt2 and Hog1. Overall, our results indicated that FadA signalling engages in mycotoxin production and A . flavus resistance to antimicrobial PAE, which provide valuable information for controlling this fungus and AF biosynthesis in pre‐ and postharvest of agricultural crops.

Establishing a Risk Assessment Framework for Marine Assets and Assessing Typhoon Lekima Storm Surge for the Laizhou Bay Coastal Area of the Bohai Sea, China - Jian Li; Dongxue Mo; Rui Li; Yijun Hou; Qingrong Liu (Journal of Marine Science and Engineering, 2022)
Effective risk assessment can reduce the economic losses and physical damage caused by marine dynamic processes, such as storm surges. Most risk assessments of marine disasters are based on regional parameters and discrete hazard grades. Targeted, multilevel, and multiangle risk assessments are urgently needed. This study focuses on specific types of affected infrastructure. We established a sensitivity matrix by considering the effects of different disaster causal factors on different types of affected infrastructure. Through this matrix, hazards, vulnerability, and emergency response and recovery capability were effectively combined in a risk assessment framework. We completed the risk calculation for multiple concurrent effects of disasters in areas with superimposed key infrastructure using complementary risk superposition. The hazard grade, vulnerability grade, and coefficient of emergency response and recovery capability were established based on the means of return period, characteristics of disaster distribution, types of affected infrastructure and disaster relief distance, and were continuous by solving functions, normal cumulative distributions, and analytic functions. On the basis of reasonable MIKE21 numerical simulation and abstract spatial distribution of vulnerable assets, we tested the rationality of the assessment system in the Lekima typhoon storm surge process. The results showed that the assessment system accurately reflected the risk of damage to the important infrastructure in terms of spatial distribution. Therefore, this risk assessment framework was suitable for the assessment of a marine dynamic disaster process in the lower Laizhou Bay coastal area of the Bohai Sea, China. Moreover, it provided a reference for disaster prevention and reduction, guided the way for decision making, and effectively reduced disaster losses.

Cytotoxic α-pyrone derivatives from Cryptocarya yunnanensis - Qian He; Yue Fan; Yu Liu; Yun-Xia You; Li Rao; Yu Su; You-Kai Xu; Bin Lin; Chuan-Rui Zhang (Natural Product Research, 2022)

A 250 m resolution global leaf area index product derived from MODIS surface reflectance data - Zhiqiang Xiao; Jinling Song; Hua Yang; Rui Sun; Juan Li (International Journal of Remote Sensing, 2022)

A 2 -FPN for semantic segmentation of fine-resolution remotely sensed images - Rui Li; Libo Wang; Ce Zhang; Chenxi Duan; Shunyi Zheng (International Journal of Remote Sensing, 2022)

Sugar Tech Special Issue: History of Sugarcane Breeding, Germplasm Development and Related Molecular Research - Prakash Lakshmanan; Phillip Jackson; G. Hemaprabha; Yang Rui Li (Sugar Tech, 2022)

Spatio-temporal characteristics of demersal fish community in the Chukchi and northern Bering Seas: significant distributional records and interannual variations in species composition and biodiversity - Ran Zhang; Puqing Song; Hai Li; Rui Wang; Yuan Li; Xing Miao; Longshan Lin; Shaoxiong Ding (Polar Biology, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

A Reliable Murine Model of Disseminated Infection Induced by Talaromyces Marneffei - Juan He; Jia-Sheng Li; Hong-Yan Xu; Yi-Qun Kuang; Jun Li; Hong-Bin Li; Zhe Li; Hui-Ling Zhou; Rui-Rui Wang; Yu-Ye Li (Mycopathologia, 2022)

Spermatogonia From Cryopreserved Testes of Critically Endangered Chinese Sturgeon Efficiently Colonized and Preferentially Proliferated in the Recipient Gonads of Yangtze Sturgeon - Huan Ye; Yutaka Takeuchi; Hao Du; Huamei Yue; Rui Ruan; Chuangju Li; Qiwei Wei (Marine Biotechnology, 2022)

MiR-582-3p participates in the regulation of biological behaviors of A549 cells by ambient PM2.5 exposure - Mei Yang; Liangliang Ju; Changlian Li; Han Cheng; Na Li; Qi Zhang; Shu Sun; Liu Ding; Xinmiao Sui; Chao Zhang; Mingwei Yang; Jiyu Cao; et al. (Environmental Science and Pollution Research, 2022)

Hierarchical porous polystyrene-based activated carbon spheres for CO2 capture - Xiaoxia Ren; Changming Zhang; Lifang Kou; Rongxian Wang; Yaqi Wang; Rui Li (Environmental Science and Pollution Research, 2022)

Long-term observations of the chemical composition, fluxes and sources of atmospheric wet deposition at an urban site in Xi’an, Northwest China - Rui-feng Li; Xi-ying Dong; Cong Xie; Liang-ju Zhao (Environmental Monitoring and Assessment, 2022)

Janibacter endophyticus sp. nov., an Endophytic Actinobacterium Isolated from the Root of Paris polyphylla Smith var. Yunnanensis - Zhen Zhang; En-Min Zhou; Cong-Jian Li; Xing-Wang Jiang; Rui-Feng Mao; Jing-Ran Liu; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2022)

Interaction of influenza A virus NS1 and cytoskeleton scaffolding protein α-actinin 4 - Yingyue Zeng; Rui Wang; Fengchao Wang; Man Zhang; Li Zhang; Chunyu Zhu; Jian Zhao; Hongsheng Liu (Virus Genes, 2022)

Evaluation of suitable qRT-PCR normalization genes for various citrus rootstocks - Wen He; Rui Xie; Huan Li; Yan Wang; Qing Chen; Yuanxiu Lin; Yunting Zhang; Ya Luo; Yong Zhang; Haoru Tang; Xiaorong Wang (Plant Biotechnology Reports, 2022)

Transcriptome Analysis Reveals Molecular Mechanisms Underlying Methyl Jasmonate-mediated Biosynthesis of Protopanaxadiol-type Saponins in Panax notoginseng Leaves - Ying Li; Yuan Lin; Bing Jia; Geng Chen; Huineng Shi; Rui Xu; Xuejiao Li; Junrong Tang; Qingyan Tang; Guanghui Zhang; Jianli Yang; Wei Fan; et al. (Journal of Plant Biology, 2022)

GIS-based spatial prediction of landslide using road factors and random forest for Sichuan-Tibet Highway - Cheng-ming Ye; Rui-long Wei; Yong-gang Ge; Yao Li; José Marcato Junior; Jonathan Li (Journal of Mountain Science, 2022)

miR-181b-5p Promotes the Progression of Cholangiocarcinoma by Targeting PARK2 via PTEN/PI3K/AKT Signaling Pathway - Zhe-Long Jiang; Fu-Xing Zhang; Hong-Liang Zhan; He-Jun Yang; Si-Yu Zhang; Zhao-Hui Liu; Yi Jiang; Li-Zhi Lv; Rui-Sheng Ke (Biochemical Genetics, 2022)

The responses of detoxification enzyme and gene expression in western flower thrips, Frankliniella occidentalis, to new challenging hosts - Wen-Bo Yue; Jun-Rui Zhi; Li Liu; Xiao-Lin Hou; Mao Ye (Arthropod-Plant Interactions, 2022)

Neobacillus paridis sp. nov., an endophyte of Paris polyphylla Smith var. yunnanensis - Peng-Chao Zhan; Cong-Jian Li; Zhen Zhang; Rui-Feng Mao; Jing-Ran Liu; Xing-Wang Jiang; Xiao-Yang Zhi; Ling-Ling Yang (Archives of Microbiology, 2022)

Cu/Zn Superoxide Dismutase and Catalase of Yangtze Sturgeon, Acipenser dabryanus: Molecular Cloning, Tissue Distribution and Response to Fasting and Refeeding - Qingchao Shi; Xiaoqin Xiong; Zhengyong Wen; Chuanjie Qin; Rui Li; Zhiyong Zhang; Quan Gong; Xiaoyun Wu (Fishes, 2022)
Superoxide dismutase and catalase are two major antioxidant enzymes in the fish antioxidant defense system, which can remove excess reactive oxygen species and protect fish from stress-induced oxidative damage. The present study aimed to clone the sequences of Yangtze sturgeon, Acipenser dabryanus, Cu/Zn superoxide dismutase (AdCu/Zn-SOD) and catalase (AdCAT), and to explore changes of gene expression in the liver and intestine during fasting and refeeding. A total of 120 fish were exposed to four fasting and refeeding protocols (fasting for 0, 3, 7, or 14 d and then refeeding for 14 d). The coding sequences of AdCu/Zn-SOD and AdCAT encoded 155 and 526 amino acid proteins, respectively, both of which were expressed mainly in the liver. During fasting, when compared to the control group, liver AdCu/Zn-SOD expression was significantly higher in the 3- and 14-d groups, whereas its intestinal expression increased significantly only in the 7-d group. Liver AdCAT expression increased significantly in the 3-, 7-, and 14-d groups. During refeeding, liver AdCu/Zn-SOD expression increased significantly in the 3-, 7-, and 14-d groups compared with those in the control group. Similarly, intestinal AdCu/Zn-SOD expression increased significantly in the 3- and 7-d groups. Moreover, intestinal AdCAT expression was significantly higher in the 3-d group than in the control group, but decreased significantly in the 14-d group. Our findings indicated that AdCu/Zn-SOD and AdCAT play important roles in protecting fish against starvation-induced oxidative stress. Yangtze sturgeon exhibited the potential to adapt to a starvation and refeeding regime.

Surface wind and vertical extent features of the explosive cyclones in the Northern Hemisphere based on the ERA‐I reanalysis data - Li‐Zhi Jiang; Shen‐Ming Fu; Jian‐Hua Sun; Rui Fu; Wan‐Li Li; Si‐Xiong Zhao; Hui Wang (International Journal of Climatology, 2022)
Although explosive cyclones (ECs) have long been a focus of research, there remains a lack of knowledge of the statistical characteristics of their associated maximum surface winds and vertical extents. This study fills this gap by conducting a targeted statistical analysis of ECs in the Northern Hemisphere using the ERA‐I reanalysis data during a 40‐year period. Some new findings are obtained: (a) The average location of formation of ECs undergoes a notable westward and equatorward shift from September to April in the next year which is consistent with the location variations of sea surface temperature's strong gradients in subtropical regions. (b) Extreme ECs with a deepening rate more than 2.0 Bergeron or with a longer lifespan more than 10 days tend to have a larger occurrence number over the Northern Atlantic Ocean than over the Northern Pacific. (c) The maximum surface wind associated with an EC tends to appear between the EC reaching its maximum deepening rate and reaching its minimum central pressure. (d) The northeastern quadrant of ECs accounts for the highest proportion of maximum surface wind and strongest wind speed, as the baroclinic energy conversion is generally strongest in this quadrant. (e) Over 60% of ECs belong to a type of vertically deep cyclone (ECs' top levels show close relationship to ascending motions within their central regions), and they tend to reach their maximum vertical extent around the time when they reach their minimum central pressures. (f) The highest top levels of ECs exhibit an overall upward extending trend as their minimum central pressure decreases or their maximum deepening rate increases.

Metabolic potentials of members of the class Acidobacteriia in metal‐contaminated soils revealed by metagenomic analysis - Rui Xu; Xiaoxu Sun; Max M. Häggblom; Yiran Dong; Miaomiao Zhang; Zhaohui Yang; Enzong Xiao; Tangfu Xiao; Pin Gao; Baoqin Li; Weimin Sun (Environmental Microbiology, 2022)
Summary The relative abundance of Acidobacteriia correlated positively with the concentrations of arsenic (As), mercury (Hg), chromium (Cr), copper (Cu) and other metals, suggesting their adaptation of the metal‐rich environments. Metagenomic binning reconstructed 29 high‐quality metagenome‐assembled genomes (MAGs) associated with Acidobacteriia , providing an opportunity to study their metabolic potentials. These MAGs contained genes to transform As, Hg and Cr through oxidation, reduction, efflux and demethylation, suggesting the potential of Acidobacteriia to transform such metal(loid)s. Additionally, genes associated with alleviation of acidic and metal stress were also detected in these MAGs. Acidobacteriia may have the capabilities to resist or transform metal(loid)s in acidic metal‐contaminated sites. Moreover, these genes encoding metal transformation could be also identified in the Acidobacteriia ‐associated MAGs from five additional metal‐contaminated sites across Southwest China, as well as Acidobacteriia ‐associated reference genomes from the NCBI database, suggesting that the capability of metal transformation may be widespread among Acidobacteriia members. This discovery provides an understanding of metabolic potentials of the Acidobacteriia in acidic metal‐rich sites.

Chemical constituents from the fruits of Piper longum L. and their vascular relaxation effect on rat mesenteric arteries - Dan Li; Rui Wang; Xiaohan Cheng; Jianfeng Yang; Yihui Yang; Huichong Qu; Sen Li; Shan Lin; Donghua Wei; Yuhua Bai; Xiaodong Zheng (Natural Product Research, 2022)

Dimeric hexylitaconic acids from the marine-derived fungus Aspergillus welwitschiae CUGBMF180262 - Jiahui Han; Na Yang; Shangzhu Wei; Jia Jia; Rui Lin; Jiangpeng Li; Hongkai Bi; Fuhang Song; Xiuli Xu (Natural Product Research, 2022)

Two new threonine-containing metabolites from fungus Curvularia inaequalis strain HS-FG-257 - Shao-Yong Zhang; Jian-Song Li; Hui Zhang; Huan Qi; Rui-Jun Wang; Chou-Fei Wu; Li-Qin Zhang; An-Liang Chen; Ji-Dong Wang; Zhi-Kui Hao (Natural Product Research, 2022)

Secondary metabolites isolated from Agrimonia pilosa Ledeb. - Hong-Rui Li; Yu-Kui Li; Jian Xiao; Cui Yang; Meng-Yuan Jiang; Kai Tian; Wei Wang; Yan-Hong Li; Xiang-Zhong Huang (Natural Product Research, 2022)

Four new indole alkaloids from the roots of Isatis tinctoria - Dongdong Zhang; Yu Sun; Yanhong Shi; Ximin Wu; Qi Jia; Kaixian Chen; Yiming Li; Rui Wang (Natural Product Research, 2022)

A feasible vibration measurement and active control method of reinforced concrete lightweight pier railway bridges for heavy-haul monorail trains - Ling-kun Chen; Li-zhong Jiang; Rui Li; Qiao Li; Ming Zhang; Nan Zhang; Jin-zhang Luo; Liang Ling; Sheng-yang Zhu (European Journal of Environmental and Civil Engineering, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

Organic-rich formation and hydrocarbon enrichment of lacustrine shale strata: A case study of Chang 7 Member - Quanyou Liu; Peng Li; Zhijun Jin; Yuewu Sun; Guang Hu; Dongya Zhu; Zhenkai Huang; Xinping Liang; Rui Zhang; Jiayi Liu (Science China Earth Sciences, 2022)

A combined transcriptomic and proteomic analysis of chrysanthemum provides new insights into petal senescence - Juanni Yao; Rui Li; Yulin Cheng; Zhengguo Li (Planta, 2022)

Molecular cloning and functional characterization of two squalene synthase genes in Atractylodes lancea - Junxian Wu; Rui Xu; Jimei Lu; Weiwei Liu; Hanwen Yu; Mengli Liu; Jing Li; Minzhen Yin; Huasheng Peng; Liangping Zha (Planta, 2022)

Roots and microbiome jointly drive the distributions of 17 phytohormones in the plant soil continuum in a phytohormone‐specific manner - Yuqiu Lu; Enzhao Wang; Zhiyu Tang; Junpeng Rui; Yanling Li; Zhixi Tang; Weiling Dong; Xiongduo Liu; Timothy S. George; Alin Song; Fenliang Fan (Plant and Soil, 2022)

Short-term grazing rather than mowing stimulates N2O production potential through enhancing the bacterial pathway in semiarid grasslands - Yingjin Song; Jinlei Li; Lei Zhong; Jianming Xue; Gaoyuan Li; Jinwu Qing; Yichao Rui; Guanyi Chen; Taogetao Baying; Frank Yonghong Li (Journal of Soils and Sediments, 2022)

Soil salinity variations and cotton growth under long-term mulched drip irrigation in saline-alkali land of arid oasis - Wenhao Li; Zhenhua Wang; Jinzhu Zhang; Rui Zong (Irrigation Science, 2022)
The sustainable development and utilization of saline-alkali land are closely related to holding fast the minimum cultivated land area of China. The change of soil salt in cotton field under long-term mulched drip irrigation (MDI) is connected with the development of the national cotton industry. From 2015 to 2019, five cotton fields with different applying years of MDI, which were reclaimed in 2004, 2008, 2010, 2012 and 2015 respectively and were saline-alkali wasteland before, were monitored continuously in the Manas River irrigation area of Xinjiang. By means of continuous location monitoring and spatial–temporal variability (For example, the monitoring data of cotton fields under MDI in 2004, 2008, 2010, 2012 and 2015, and in the year of 2015 were counted as 12, 8, 6, 4 and 1 years, respectively), the spatial–temporal variations of soil salt and ions in cotton field with 1-16a MDI technology were presented. The cotton growth characteristics and its main influencing factors were also analyzed in the study. The results showed that saline-alkali cotton field experienced changed from intensive saline soil to moderate saline soil and finally to non-saline soil under long-term MDI. The change of soil salt and the response of cotton growth to soil salt were divided into three typical stages. Firstly, soil desalinated rapidly in 1-4a MDI cotton field, which the annual average desalination rate was 24.93% in 0–100 cm soil layer (root zone). Additionally, the survival rate of cotton rocketed from 1.48% to 42.04%, and yield increased sharply from 72.43 kg ha −1 to 3075.90 kg ha −1 . Soil desalination was lower in 5-11a MDI cotton field, which the annual average desalination rate was 10.92% at the root zone. The annual survival rate and yield of cotton increased by 6.26% and 5.18%, respectively. After 12a MDI, the soil salt in cotton field tended to be generally constant, which the average salt content in root zone was less than 2.49 g kg −1 . The survival rate of cotton was stable above 90.39%, and the yield per unit area exceeded 5401.32 kg ha −1 . Ions, sodium absorption ratio and Cl − and SO 4 2− equivalent ratio (CSER) in cotton soil also decreased with the extension of MDI. Salt composition changed year by year, but the type of intensive saline soil had always been chloride-sulphate solonchak (0.2 < CSER < 1). In practice, with a higher irrigation quota and ideal irrigation water quality, the soil salt environment of saline-alkali soil MDI cotton field had developed in favor of cotton growth in an oasis irrigation area. However, this management practice caused between 124.21–143.61 mm of water resources waste. Therefore, we should further enhanced the consciousness of water-saving and implemented quota management in practice.

Peripheral Administration of an Opioid Peptide Analog Ameliorates Morphine-Produced Hyperalgesia in a Spared Nerve Injury Model - Yuan Wang; Meng-tao Ma; Jing Wang; Chao-zhen-yi Han; Kai Li; Qiao-min Ru; Na Li; Xin Liu; Rui Wang (International Journal of Peptide Research and Therapeutics, 2022)

Air pollution increased risk of reproductive system diseases: a 5-year outcome analysis of different pollutants in different seasons, ages, and genders - Ya Li; Juan Du; Shanshan Lin; Huihui He; Rui Jia; Weihong Liu (Environmental Science and Pollution Research, 2022)

Existing form and distribution of fluorine and phosphorus in phosphate rock acid-insoluble residue - Rui Li; Weilong He; Jiangfei Duan; Shengxia Feng; Ziyu Zhu; Yu Zhang (Environmental Science and Pollution Research, 2022)

Prenatal air pollution exposure increases the risk of macrosomia: evidence from a prospective cohort study in the coastal area of China - Changlian Li; Liangliang Ju; Mei Yang; Qi Zhang; Shu Sun; Jiyu Cao; Rui Ding (Environmental Science and Pollution Research, 2022)

Mutual impacts and interactions of antibiotic resistance genes, microcystin synthetase genes, graphene oxide, and Microcystis aeruginosa in synthetic wastewater - Shichao Wu; Xiyan Ji; Xin Li; Jing Ye; Wenwu Xu; Rui Wang; Meifang Hou (Environmental Science and Pollution Research, 2022)

Quantitative methods for predicting underground construction waste considering reuse and recycling - Rui Chen; Lanxin Li; Kai Yang; Fumin Ren; Chenggang Xi; Yang Lin; Hai Zheng (Environmental Science and Pollution Research, 2022)

Variations in bacterial and archaeal community structure and diversity along the soil profiles of a peatland in Southwest China - Wei Li; Mingmo Luo; Rui Shi; Defeng Feng; Zhenan Yang; Huai Chen; Bin Hu (Environmental Science and Pollution Research, 2022)

The specialized mitotic behavior of human embryonic stem cells - Rui Lyu; Xuemei Wu; Nan Ma; Difei Wang; Shuang Sun; Youguang Luo; Jun Zhou; Xinyi Lu; Min Liu; Dengwen Li (Cell and Tissue Research, 2022)

Laser ablation inductively coupled plasma mass spectrometry analysis of Chinese lead-barium glass: combining multivariate kernel density estimation and maximum mean discrepancy to reinterpret the raw glass used for producing lead-barium glass - Qian Ma; Rui Wen; Yifan Yu; Long Wang; Man Li; Luwu Cai; Li Ping; Zhiqiang Zhao; Dong Wang; Xiang Wang; Ruoyu Shi; A. Mark Pollard (Archaeological and Anthropological Sciences, 2022)

Characteristics of an ore-controlling shear zone in the Cigou-Zaoyang gold mine area of Ankang, South Qinling Mountains, China - Hujun He; Yichen Zhao; Jian Zhang; Xingke Yang; Rui Xing; Wei Li (Arabian Journal of Geosciences, 2022)

Kangiella shandongensis sp. nov., a novel species isolated from saltern in Yantai, China - Li-Yang Peng; Rui Yin; Shu-Kun Gao; Hui-Ning Jiang; Xiao-Xiao Liu; Yu Ma; Yan-Xia Zhou (Antonie van Leeuwenhoek, 2022)